Multifunctional composite Si and C-based particles
Patent Information
- Application Number
- KR1020267024352
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2024-12-30
- Publication Date
- 2026-09-01
Smart Images

Figure PCT00042_ABST
Abstract
Description
Technology Field
[0001] Cross-reference regarding related applications
[0002] The present application claims the benefit of U.S. Provisional Application No. 63 / 616,188, filed December 29, 2023, titled “Multifunctional Composite Si-particles”; U.S. Provisional Application No. 63 / 571,951, filed March 29, 2024, titled “Multifunctional Composite Si-particles”; U.S. Provisional Application No. 63 / 571,965, filed March 29, 2024, titled “Polymer Brush Coated Silicon-Carbon Composite Materials”; and U.S. Provisional Application No. 63 / 571,715, filed March 29, 2024, titled “Enhanced Performance of Current Collectors through Polymer Brush Coating”, all of which are incorporated herein by reference in their entirety.
[0003] field
[0004] The present disclosure provides a method for forming a polymer brush on Si and C-based particles, thereby enabling easy large-scale fabrication of a polymer brush covalently bonded to Si and C-based particles. In particular, the method allows for easy control of graft density due to the formation of multifunctional composite Si and C-based particles. The present disclosure also provides multifunctional composite Si and C-based particles as well as multifunctional composite Si and C-based particles on which a polymer brush is formed. The present disclosure also provides a system for forming polymer brush-coated particles and a device comprising polymer brush-coated particles, wherein the device may also include a polymer brush-coated electrode. Background Technology
[0005] Silicon particles are used in various applications, including anode materials for electronics, solar cells, semiconductors, and electrochemical cells.
[0006] The properties of materials change as their size approaches the nanoscale. For example, silicon nanoparticles generally exhibit significantly higher reactivity compared to their bulk versions. This increase in reactivity may be due to the increase in surface area relative to bulk volume as particle size decreases. Additionally, smaller particles generally possess greater internal strain, which can further enhance surface reactivity.
[0007] In particular, while bulk silicon generally forms only a thin oxide layer on its surface upon interaction with oxygen and water, the thickness and non-uniformity of the oxide layer increase significantly as the particle size decreases to less than 100 nm, and nanometer-sized Si particles can be completely degraded in the presence of oxygen. This applies particularly to untreated and H-terminated Si particles with highly reactive Si-Si bonds. Therefore, Si particle surfaces are often passivated with organic molecules (e.g., alkyl chains) to make the Si particles more resistant to oxidation.
[0008] In addition, the increased reactivity of Si particles compared to bulk silicon in the form of, for example, silicon wafers implies that Si particles generally have a high affinity for dissolution in water and oxygen or are incompatible with typical polar and hydrophilic solvents that possess -OH groups (e.g., acetone, isopropanol, etc.). However, the addition of passivation organic moiety can change compatibility with various solvents.
[0009] Silicon is particularly useful as an anode storage material in lithium-ion cells due to its very high lithium absorption capacity compared to carbon-based storage materials. However, volume changes that occur when lithium forms alloys with silicon emerge as a problem, which can lead to significant performance loss over extensive cycling. Additionally, the formation of a surface-electrode interface (SEI) can result in significant gas generation during initial cycling. Therefore, there is a continuous need to provide silicon materials that can be used as anode materials to address these issues.
[0010] There is still a need for methods to functionalize Si particles to provide particles suitable for use in various applications. It would be particularly useful to provide Si particles with defined solubility and surface properties.
[0011] Likewise, there is interest in improving graphite particles, carbon-coated silicon particles, and Si / C composite particles. While the electrochemical reactions of graphite are intercalation (during charging) and deintercalation (during discharging), the corresponding charge / discharge cycling of silicon is lithiation and delithiation; however, the results of these cycling are similar—volume expansion (during charging) and contraction (during discharging)—but the degree of change is much smaller than the volume expansion of up to 400% associated with silicon, approximately 5 to 10%. Therefore, one of the failure mechanisms of capacity loss is that the anode components—silicon, graphite, carbon-coated, and / or Si / C composite particles—lose electrical connectivity to the entire electrochemical circuit of the energy storage device, that is, the particles lose electrical connectivity as they physically detach from the circuit due to repeated volume expansion and contraction cycles.
[0012] To address these issues, significant progress has been made in applying nanoscale modifications and integrating various materials to enhance the performance of Si and Si-based anodes in LIBs. Various methods, including nanostructure modifications and material integration, have been explored to mitigate problems such as volume expansion and SEI formation. Specifically, integrating specific materials into Si anodes has demonstrated potential for mitigating volume expansion, improving contact area with the electrode and electrolyte, enhancing lithiation / delithiation rates, and ultimately improving battery performance. However, existing strategies to enhance Si anode performance generally involve complex nanoscale modifications, material combinations, and electrolyte control. These approaches often hinder the feasibility of large-scale manufacturing due to limitations in scalability and reproducibility. Furthermore, the integration of additional materials or additives to improve anode performance can increase production costs and cause compatibility issues with existing battery manufacturing processes. In contrast, SiOx materials have shown some advantages in anode applications due to less severe volume change effects. However, SiOx materials still cannot completely overcome the general problems associated with Si-based anodes.
[0013] Consequently, Si / C composites are receiving widespread attention in the development of silicon anodes, where carbon materials serve as a protective and supporting framework for silicon. The selection of carbon in silicon mixtures is due to its low-cost manufacturing, structural and compositional flexibility, and the feasibility of large-scale fabrication. Common types of carbon components in Si / C include silicon covered with a carbon coating (or carbon shell) and silicon embedded in a carbon matrix.
[0014] The simplest approach to fabricating Si / C composites is to produce silicon particles covered with carbon materials. For example, Wang et al. reported a core-shell style Si / C anode material (J. Power Sources, 2011, 196, 10, 4811-4815). The silicon component consisted of amorphous Si clusters and regular SiO2 domains, and the carbon layer was prepared as an epoxy resin precursor through heat treatment. This material provided a reversible specific capacity of approximately 800 mAh / g. Similarly, a yoke-shell structure was utilized in Si / C composite designs to allow for internal void spaces to accommodate silicon volume changes. Liu et al. reported a pomegranate-shaped yolk-shell Si / C anode material in which primary silicon nanoparticles were encapsulated by a conductive carbon shell having sufficient internal free space for volume expansion, and secondary composite particles were encapsulated by a thicker carbon layer to reduce direct electrolyte contact (Nat. Nanotechnol, 2014, 9, 187-192). Due to the protection provided by the carbon structure, excellent cycling characteristics were achieved, with a capacity retention rate of 97% after 1,000 cycles. In addition to the void space between the yolk and the shell, porous structures can also be fabricated within the silicon itself (i.e., porous silicon materials). For example, Liu et al. developed a pitch-pyrolytic carbon-coated nanoporous Si / graphite (NP-SiC / Gr) composite, in which nanoporous silicon was prepared by chemical dealloying of an Al-Si alloy and subsequent pitch coating (Energy Fuels, 2023, 37, 6, 4624-4631). When mixed with graphite material, NP-Si@C / Gr provided a reversible capacity of 764.2 mAh / g, which is the reversible capacity of NP-SiC / Gr.
[0015] Another approach to fabricating Si / C composites is to embed silicon particles in a carbonaceous matrix as a hosting framework. For example, Xu et al. reported SiOx particles embedded between the interior and surface of graphite by exfoliating and restoring the structure of artificial graphite (Adv. Funct. Mater. 2018, 28, 1705235). The resulting SiOx anode provided a high reversible capacity of 645 mAh / g with a capacity retention rate of approximately 90% after 500 cycles. In another example, Kwon et al. developed a Si / C structure with silicon nanocrystals embedded in micro carbon balls (Nano Lett., 2020, 20, 1, 625-635). These Si / C composites were fabricated using a microemulsion method and low-cost corn starch as a biomass precursor, and provided a capacity of 1,800 mAh / g with a retention rate of 80% over 500 cycles.
[0016] However, carbon material coatings or matrices cannot completely resolve the inherent volume change issues of Si materials. The repeated expansion and contraction of Si-based anode materials will inevitably lead to electrode complex failure during long-term battery operation. Therefore, it is necessary to further develop another level of structurally controlled components outside of the carbon coating for Si materials. Additionally, it should be noted that the mass production of Si-based anode materials must rely on low-cost Si sources (e.g., silicon kerf, metallurgical Si, or ferrosilicon), inexpensive processes, and economical carbon sources. These manufacturing factors will limit the application of sophisticated Si / C material designs. There remains a critical need for innovative approaches capable of providing robust, cost-effective, and scalable Si-based LIBs that can meet the stringent requirements of commercial applications.
[0017] As the demand for high-performance lithium-ion batteries (LIBs) continues to grow, particularly in the electric vehicle (EV) market, ongoing research efforts are focused on material innovation to improve performance, reduce overall battery weight, and lower manufacturing costs. In this context, current collectors (CC) play a critical role, as the weight of aluminum (Al) and copper (Cu) significantly impacts the price, weight, and energy density of LIB systems. Among various strategies to advance LIB technology, significant attention has been focused on the development of lithium metal batteries (LMBs) as a promising direction for next-generation energy storage systems. Lithium metal possesses a high theoretical capacity of 3,860 mAh / g, lightweight characteristics (0.534 g / cm³), and the lowest electrochemical potential (-3.04 V vs. standard hydrogen electrode). LMBs utilizing lithium metal as the anode offer distinct advantages over conventional LIBs, including higher theoretical energy density and the potential for lightweight designs. However, the commercial feasibility of LMBs is hampered by inherent issues such as dendrite formation and electrolyte instability. To overcome these obstacles, extensive research initiatives have been undertaken, including separator modification, electrolyte composition optimization, electrolyte additive integration, exploration of solid or gel electrolytes, application of protective layers to lithium metal anodes, and development of artificial solid electrolyte interphase (SEI) layers. Additionally, efforts have been made to improve electrochemical stability through current collector (CC) modification. These advancements highlight a multifaceted approach to advancing battery technology and meeting the evolving demands of various industries.
[0018] outline
[0019] In one aspect of the present disclosure, a composite particle is provided, wherein the composite particle comprises a silicon core decorated with a first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to at least a silicon core, and a second moiety comprising a second anchoring component and a functional group covalently bonded to the silicon core. The composite particle has an average diameter (D) of about 10 nm to about 500 nm as measured by dynamic light scattering. [4,3] It may have 50). The first and second anchoring components are -C ‡ (R A1 )(R A2 )CH(R A3 )-, -C ‡ HCH-, or -C ‡ It can be selected from MeCH-, where C ‡ represents carbon covalently bonded to the silicon of the Si particle, and R A1 , R A2 , R A3 Each is independently selected from H or Me. The polymerization initiator may include a radical stabilizer (Rad) and a leaving group (LG). The polymerization initiator may be Rad-LG, where Rad is covalently bonded to the remainder of the first moiety and -(C6(R Rad2 )4)-C*(R Rad1 )2, -(C 10 (R Rad2 )6)C*(R Rad1 )2-, -C*(R Rad3 )2, -OC(O)C*(R Rad1 )2, or -NR Rad1 C(O)C*(R Rad1 Selected from )2, where C* represents the carbon attached to LG, and each R Rad1 represents independently H or methyl, and each R Rad2 is independently H or R Rad3 Represents, and R Rad3represents methyl, and LG is selected from Cl, Br, or I. The functional group is H, -C6H5, -C6F5, -C(O)OR FG3 , or can represent CN, where R FG3 represents CH3 or tertiary-butyl. The relative surface stoichiometry of the first moiety may be at least 0.5%. The silicon core may comprise crystalline silicon.
[0020] In one aspect of the present disclosure, a method for forming a composite particle is provided, the method comprising: providing a silicon particle, a first moiety precursor comprising a first anchorable component and a first functional group (e.g., a polymerization initiator), and a second moiety precursor comprising a second anchorable component and a functional group; and decorating the silicon particle by reacting the first anchorable component of the first moiety precursor to form a first anchoring component of the first moiety and reacting the second anchorable component of the second moiety precursor to form a second anchoring component of the second moiety, wherein the first anchoring component and the second anchoring component are covalently bonded to the silicon particle. The composite particle may be an aggregate of particles, said aggregate having an outermost surface and a plurality of inner surfaces, and comprising an outer composite particle and an optional inner particle, wherein the optional inner particle comprises a silicon core, and the outer composite particle comprises a silicon core and an outer surface region, said outer surface region comprising a region decorated with first and second moieties covalently bonded to the silicon core of the outer composite particle through first and second anchoring components, said decorated region of the outer surface region of the outer composite particle forms the outermost surface of the aggregate, and none of the surfaces of the optional inner particle form part of the outermost surface of the aggregate.
[0021] In one aspect of the present disclosure, a method for forming a composite particle is provided, the method comprising the steps of providing a silicon particle, a first moiety precursor comprising a first anchorable component and a polymerization initiator, and a second moiety precursor comprising a second anchorable component and a functional group, and decorating the silicon particle by reacting the first anchorable component of the first moiety precursor to form a first anchoring component of the first moiety and reacting the second anchorable component of the second moiety precursor to form a second anchoring component of the second moiety, wherein the first anchoring component and the second anchoring component are covalently bonded to the silicon particle. In the method, the silicon particle may be exposed to HF to form a Si-H moiety on at least a portion of its surface prior to reaction with the first and second moiety precursors. The method may be such that the first and second moiety precursors are immobilized on the surface of the Si particle in the same step. The ratio of the first moiety precursor to the second moiety precursor used to decorate the Si particles can be 1:9 to 9:1. The silicon core has an average diameter (D) of about 10 nm to about 500 nm, as measured using dynamic light scattering. [4,3] 50) may be included. The first moiety precursor may include 4-vinyl benzyl chloride, and the second moiety precursor may include tertiary-butyl acrylate, styrene, pentafluorostyrene, or acrylonitrile.
[0022] In one aspect of the present disclosure, a polymer brush composite particle is provided, wherein the polymer brush composite particle comprises a silicon core decorated with a first moiety comprising a polymer moiety and a first anchoring component covalently bonded to at least a silicon core, and a second moiety comprising a second anchoring component and one or more functional groups. The polymer moiety may have a linear polymer chain having an average length of about 2 repeating units to about 1,000 repeating units.
[0023] In one aspect of the present disclosure, a method for forming a polymer brush composite particle is provided, the method comprising the steps of: providing a composite particle comprising a silicon core decorated with a first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to at least a silicon core, and a second moiety comprising a second anchoring component and a functional group covalently bonded to the silicon core; forming a polymerization reaction composition comprising one or more polymerization catalysts and one or more monomers; and exposing the composite particle to the polymerization reaction composition. The polymer brush may be synthesized by surface-initiated polymerization (SIP). In the method, the polymerization reaction composition may be formed from a polymerization composition comprising at least one dormant transition metal catalyst, an activator comprising an oxygen scavenger, and one or more monomers, wherein one or more monomers may be provided as part of the polymerization composition, part of the activator, or as a separate composition.
[0024] The methodology described herein provides decorated silicon particles having controllable solubility / dispersibility. For example, the decorated particles may have a combination of a hydrophilic layer and a hydrophobic layer, enabling solubility adjustment. Additionally, the particles have a passivated silicon surface, which exhibits excellent stability under conditions that could lead to reactions such as oxidation of untreated silicon particles.
[0025] The present disclosure provides a method for forming a polymer brush on Si and C-based particles, thereby enabling easy large-scale manufacturing of a polymer brush covalently bonded to Si and C-based particles. In particular, the method allows for easy control of graft density due to the formation of multifunctional composite Si and C-based particles. The present disclosure also provides multifunctional composite Si and C-based particles as well as multifunctional composite Si and C-based particles on which a polymer brush is formed.
[0026] The present disclosure relates to a scalable technique for fabricating polymer brushes on current collectors customized for electrochemical cells comprising alkali metal-based or anode-free systems. This technique enables the creation of multifunctional current collectors having various polymer brush configurations. Furthermore, the present disclosure introduces a method for fabricating multifunctional current collectors that utilize the enhanced lithium affinity imparted by the polymer brushes to promote uniform lithium deposition in some embodiments and optimize performance in alkali metal-based or anode-free configurations. One embodiment of the present disclosure introduces a polymer brush-based primer for electrochemical cells, and more specifically for electrodes of such cells.
[0027] The present disclosure provides a structure for a device comprising a lithium battery, which combines a polymer brush on Si and C-based particles and a polymer brush on a current collector. Brief explanation of the drawing
[0028] Embodiments of the present disclosure are illustrated in the accompanying drawings. The drawings are not intended to limit the scope of the present disclosure in any way. Figure 1a shows a schematic cross-section of a decorated Si particle. FIG. 1b is a conceptual depiction of the immobilization of first and second moieties on the surface of Si particles to form decorated particles (arrow 1) and the subsequent formation of a polymer brush on the decorated particles (arrow 2). Figure 2 shows FTIR spectra for five reactions performed with different relative ratios of tert-butyl acrylate (tBA) and 4-vinylbenzyl chloride (4-VBC). The number of each spectrum is Table 1 It corresponds to the reaction number that can be seen in. Figure 3 shows the relative surface stoichiometry of 4-VBC in co-grafting experiments of 4-VBC and tBA as a function of the fraction of 4-VBC in solution. Figure 4 shows thermogravimetric analysis (TGA) of poly(tert-butyl methacrylate) (PtBA) and poly(methacrylic acid) (PMAA) polymer brushes (PB) grown from Si particles decorated with a tBA / 4-VBC solution in a 90:10 ratio. The dashed line shows the decorated Si particles before PB formation. The light gray solid line shows the particles with the poly(methacrylic acid) polymer brushes. The dark gray solid line shows the particles with the poly(tert-butyl methacrylate) polymer brushes. Figure 5 shows FTIR transmission spectra for Si nanomaterials having a base layer of tBA / 4-VBC in a ratio of 90:10, with PtBA polymer brushes (curve number 1) and PMAA polymer brushes (curve number 2), respectively. Figure 6a shows the FTIR spectra for five reactions performed with different relative ratios of pentafluorostyrene and 4-vinylbenzyl chloride (4-VBC). The number of each spectrum is Table 6 It corresponds to the reaction number that can be seen in. Figure 6b shows details of the spectrum of Figure 6a. Figure 7 shows the raw data for the 30:70 ratio co-graphing experiment of PFS and 4-VBC fitted with three components in the top diagram and the relative residuals from the data fitting in the bottom diagram. Figure 8 shows the relative surface stoichiometry of 4-VBC as a function of the fraction of 4-VBC in solution. Figure 9 shows thermogravimetric data indicating polymer brush formation on a mixed layer of PFS / 4-VBC. Figure 10 shows the KBr FTIR spectrum for a process of forming a poly(tert-butyl methacrylate) polymer brush (curve number 2) from Si particles (curve number 1) decorated with a 10:90 4-VBC / PFS reaction mixture composition, and finally removing the tert-butyl group to reveal a poly(methacrylic acid) polymer brush (curve number 3). Figure 11 shows the FTIR spectra obtained from the co-grafting of acrylonitrile and 4-vinylbenzyl chloride. The number of each spectrum is Table 10 It corresponds to the reaction number that can be seen in. Figure 12 shows the relative surface stoichiometry of 4-VBC upon co-grafting with acrylonitrile as a function of the fraction of 4-VBC in solution. Figure 13 shows FTIR spectra obtained by varying the concentration of 4-VBC during the hydrosilylation reaction. The number of each spectrum is Table 14 It corresponds to the reaction number that can be seen in. Figure 14 shows the normalized peak area for 4-VBC as a function of the solution concentration of 4-VBC. FIG. 15a shows the FTIR spectra of Si nanomaterials modified with tertiary-butyl acrylate (1) and Si nanomaterials modified with acrylic acid (2) obtained by de-tertiary-butylation of Si nanomaterials modified with tertiary-butyl acrylate. Figure 15b shows details of the spectrum of Figure 15a. FIG. 16 shows the particle size distribution for various process steps 1 to 4: 1) the original Si nanomaterial before any treatment and etching. 2) the Si nanomaterial after sonication, HF etching, and grafting onto 4-VBC. 3) the Si nanomaterial after the formation of a poly(tert-butyl methacrylate) polymer brush from the surface of the Si nanomaterial, and finally 4) the Si nanomaterial after de-tert-butylation to form a tethered poly(methacrylic acid) polymer brush from the surface of the Si nanomaterial. Figure 17 shows the FTIR spectrum of Si nanomaterials modified with a poly(methacrylic acid) polymer brush formed on particles decorated with 4-VBC. FIG. 18a shows the FTIR spectra of untreated Si nanomaterial (3), HF-etched Si nanomaterial (2), and the same material (1) after a diazonium-initiated hydrosilylation reaction with 100% tertiary-butyl acrylate to decorate Si particles. Figure 18b shows details of the spectra (1) and (2) of Figure 18a. Figure 19 shows the ATR FTIR spectrum of Si nanomaterials with poly(methacrylic acid) polymer brushes (top spectrum) and the ATR FTIR spectrum of the same material after titration with LiOH to a final pH value of 7 (bottom spectrum). Figure 20 shows titration data for Si nanomaterials modified into a poly(methacrylic acid) polymer brush and titrated with lithium hydroxide in an aqueous solution of 0.1 M LiNO3. Figure 21 shows a transmission electron microscope micrograph of silicon nanoparticle aggregates. FIG. 22 shows a schematic cross-sectional representation of an electrochemical cell including an anode according to the present disclosure, for example, a secondary lithium-ion cell. Figure 23 shows the IR spectra for graphite-I (spectrum 1), graphite-PtBMA (spectrum 2), graphite-PMAA (spectrum 3), and graphite-PMAA-Li (spectrum 4). FIG. 24 shows a schematic cross-section of a polymer brush decorated on a graphite-carbon surface of a Si / C composite material. After manufacturing the Si / C composite material, an conformal carbon coating may be applied to the surface before decorating the polymer brush. Silicon nanoparticles (31) are embedded within a carbon matrix (32), and the outer layer (33) consists of a graphite-carbon coating designed to improve conductivity and stability. Finally, the polymer brush (34) on the outer surface improves adhesion. FIG. 25 shows a diagram illustrating a polymer brush for decorating porous silicon. After the graphite-carbon coating step, the polymer brush can be applied to both the inner and outer surfaces of the porous silicon. Porous silicon particles (41) having open pores (42) are coated with a carbon layer, and the carbon layer is decorated with polymer brushes (44 and 45). Figure 26 shows a process flow diagram for the mechanochemical synthesis of Si / C composites. Figure 27 shows a process flow diagram for the MG-Si-based synthesis of Si / C composites. Figure 28 shows a process flow diagram for the silica-based synthesis of Si / C composites. Figure 29 shows a process flow diagram for silicon nanoparticle-based synthesis of Si / C composites. FIGS. 30a and FIGS. 30b show an electrode comprising an electrically conductive support and a polymer brush layer according to one embodiment described herein. Layer 1 is referred to as an anchoring layer and is located near the surface of the electrically conductive support layer 2. A polymer brush layer (layer 3) may be initiated from this anchoring layer. Layer 4, referred to as an electroactive layer, may comprise either a cathode or an anode active material. In an anode-free battery configuration, lithium ions migrate from an electrolyte solution during the battery cycling process to form a metallic lithium layer on the surface of the electrically conductive support decorated with a polymer brush. FIG. 31 shows a polymer brush layer comprising a first and / or second moiety (23) attached to an electrically conductive support (layer 22) according to one or more embodiments described herein. A polymer brush (24) is grown from an initiator moiety (23). FIG. 32 depicts a process flow diagram schematically illustrating the steps involved in implementing a method for creating an electrode structure as described in the present specification. Specific details for implementing the invention
[0029] details
[0030] A method for forming composite particles and composite particles covalently bonded to polymer brushes are disclosed herein. The composite particles are also included as described by the present disclosure.
[0031] Si particles
[0032] The present disclosure relates to composite particles comprising a silicon core. The silicon core of the present disclosure may be a silicon nanoparticle (Si-nanoparticle). The Si-nanoparticle may have an average diameter (D50) of about 10 nm to about 500 nm, e.g., about 25 nm to about 300 nm, e.g., about 50 nm to about 200 nm, e.g., about 75 nm to about 150 nm. For specific applications, the average diameter (D50) may be about 50 nm, about 75 nm, about 100 nm, about 125 nm, about 150 nm, about 175 nm, or about 200 nm.
[0033] As used herein, "diameter" refers to D measured using dynamic light scattering. [4,3] It refers to the volume-weighted average diameter, which is measured, for example, using a Microtrac Nanotrac Flex. Using this methodology, the diameter of non-spherical particles can be reported as the diameter of a sphere of the same volume. Therefore, the "average diameter" used herein is the median value (D50) of this indicator, and sometimes D [4,3] It is referred to as an average diameter of 50.
[0034] A silicon core can have any shape. For example, a silicon core can be spherical.
[0035] The silicon core may suitably have an aspect ratio of 1:1 to 3:1, such as 1:1 to 2:1, or even 1:1 to 3:2.
[0036] "Aspect ratio" refers to the ratio of the longest dimension to the shortest dimension of a particle.
[0037] The silicon core can be crystalline. For example, the silicon core can be single-crystal or polycrystalline.
[0038] Composite particles
[0039] The composite particle may include a silicon core decorated with at least two moieties, refer to FIG. 1a. Each of the two moieties may be covalently bonded to the silicon core through an anchoring component.
[0040] In the context of the present disclosure, decoration of a particle / core means that an organic molecule is covalently bonded to said particle / core.
[0041] A composite particle comprising a silicon core may be decorated with at least a first moiety comprising a first anchoring component and a first functional group (e.g., a polymerization initiator) covalently bonded to the silicon core, and a second moiety comprising a second anchoring component and a second functional group covalently bonded to the silicon core.
[0042] The composite particle may alternatively be described as a silicon core surrounded by a base layer, said base layer comprising first and second moieties covalently bonded to the silicon core.
[0043] To form the particles of the present disclosure, silicon particles are reacted with components for forming first and second moiety. The components for forming the first and second moiety may also be referred to as the first moiety precursor and the second moiety precursor, respectively. The reaction between the Si particles and the first and second moiety precursors results in the immobilization of said precursors on the surface of the Si particles. The immobilization reaction is depicted in FIG. 1b (arrow 1).
[0044] Anchor-capable components and anchoring devices
[0045] Both the first and second moiety precursors contain an anchorable component (A'). The anchorable component may be the same or different for the different moiety precursors.
[0046] By reacting the anchorable component of each of the first and second moiety precursors with the surface of the Si-particle, a covalent bond is formed between the anchorable component and the Si-particle, thereby forming an anchoring component (A), that is, a component of the moiety covalently bonded to the silicon core. Thus, the first and second moiety can be covalently bonded to the surface of the Si-particle through the anchoring component. Accordingly, the first and second moietys corresponding to the first and second moiety precursors differ in that the anchorable component (A') of the precursor reacts to form the anchoring component (A). The process of anchoring the first and second moiety to the surface may be referred to as immobilization. Hydrosilylation is an example of an immobilization technique that involves the addition of Si-H across unsaturated bonds.
[0047] The surface of Si particles can generally contain -OH groups and bridge -O- groups due to the natural oxidation of silicon by atmospheric oxygen. In order to immobilize anchorable groups on the surface of silicon particles through Si-C bonds, it may be necessary to convert the oxidized Si surface to provide an H-terminated Si surface.
[0048] Therefore, Si particles can be treated to form Si-H groups on at least a portion of the surface of the silicon particles. Pretreatment to form Si-H groups may include exposure to hydrogen fluoride (HF). The pretreatment removes Si-O bonds to form Si-H bonds (i.e., H-terminal Si-surfaces). For example, the pretreatment removes the silicon surface layer containing Si-O groups, resulting in hydrogen passivation of the surface as shown below:
[0049]
[0050] Pretreatment ensures that the surface of the Si particles is at least partially H-terminated. This means that at least 50%, for example, at least 75%, for instance, at least 85%, for instance, at least 90%, for instance, at least 95% of the Si atoms on the surface have Si-H bonds.
[0051] A general reaction scheme for the reaction between the H-terminal Si-surface and the moiety precursor can be described as follows:
[0052]
[0053] As is evident from this diagram, the moiety precursor can be described as follows:
[0054]
[0055] Here, A' can be an anchorable component, Z can be a linker group, and FG can be a functional group.
[0056] The corresponding moiety can be described as follows:
[0057]
[0058] Here, A can be an anchoring component, Z can be a linker group, and FG can be a functional group.
[0059] Anchorable components can generally contain unsaturated groups capable of performing a hydrosilylation reaction with the H-terminal Si-surface. Therefore, the anchoring group can be covalently bonded to the silicon surface through Si-C bonds.
[0060] The hydrosilylation reaction with the H-terminal Si surface requires the cleavage of Si-H bonds to form surface Si radicals. Homogeneous cleavage of Si-H bonds occurs at temperatures above 120°C, and the reaction can be carried out, for example, at T > 150°C. Some compounds having anchorable groups compatible with these high temperatures (e.g., compounds with a boiling or decomposition point > 150°C) will react with the H-terminal Si surface under heat treatment. This can be depicted as shown in the reaction schematic below:
[0061]
[0062] Diazonium salts provide a suitable option for direct reaction with H-terminated silicon surfaces at much lower temperatures, down to room temperature of ~20°C, as described below:
[0063]
[0064] In the case of the diazonium activation reaction, the counterion (X - ) is chloride (Cl - ), bromide (Br - ), tetrafluoroborate ([BF4] - ), or tosylate ( p -H3CC6H4SO3 - It can be an organic or inorganic anion such as ).
[0065] However, diazonium salts are more commonly used as co-reactants to activate the H-terminal Si-surfaces of Si-nanoparticles, forming radicals capable of reacting with suitable anchorable groups. Other suitable co-reactants are iodine salts (suitable counterion X, such as those listed above for diazonium salts). - It is selected from radical initiators such as (having), or AIBN (azobis-isobutyronitrile).
[0066] Hydrosilylation via diazonium-initiated radical generation can be described below:
[0067]
[0068] Hydrosilylation initiated by the common radical-forming species K, activated by heat treatment at T < 120°C, is described below:
[0069]
[0070] Here, K can be a radical-forming species such as azobisisobutyronitrile (AIBN).
[0071] Therefore, surface decoration by the first and second moiety can suitably occur through hydrosilylation, particularly through hydrosilylation via diazonium-initiated radical generation.
[0072] When a hydrosilylation reaction is used for immobilization, the anchorable component (A') generally contains an unsaturated carbon moiety, whereas the anchoring component (A) may be a saturated version thereof. For example, the anchorable component may contain an alkene group, which is converted into an anchoring component containing an alkane group through the immobilization reaction. Alternatively, the anchorable component may contain an alkyne group, which is converted into an anchoring component containing an alkene group through the immobilization reaction. Exemplary pairs of anchorable components / anchoring components may be selected from ethenyl / ethylene, 1-methylethenyl / 1-methylethyleneyl, 2-methylethenyl / 2-methylethyleneyl, 1,1-dimethyl-ethen-yl / 1,1-dimethylethyleneyl, 1,2-dimethylethenyl / 1,2-di-methylethyleneyl, 1,1,2-trimethyl-ethen-yl / 1,1,2-trimethylethyleneyl, or ethenyl / ethenyl.
[0073] The anchorable component / anchoring component can suitably be selected from ethenyl / ethylenyl.
[0074] Therefore, A' is R A1 (R A2 )C=C(R A3 It can be selected from )-, HCC-, or MeCC-, where R A1 , R A2 , RA3 Each can be independently selected from H or methyl (Me). A' is suitably R A1 (R A2 )C=C(R A3 It can be selected from )-.
[0075] Likewise, A is -C ‡ (R A1 )(R A2 )CH(R A3 )-, -C ‡ HCH-, or -C ‡ It can be selected from MeCH-, where C ‡ represents carbon covalently bonded to the silicon of the Si particle, and R A1 , R A2 , R A3 is independently selected from H or Me, respectively. A is -C ‡ (R A1 )(R A2 )CH(R A3 Can be selected from )-. R A1 and R A2 can represent H, and R A3 can represent H or Me.
[0076] Above, an exemplary reaction scheme between the Si surface and the moiety precursor is illustrated. The same reaction can be applied to both moiety precursors.
[0077] "First and second moiety (precursor)" means "first moiety, second moiety, first moiety precursor, or second moiety precursor." Likewise, "first moiety (precursor)" means "first moiety or first moiety precursor," whereas "second moiety (precursor)" means "second moiety or second moiety precursor."
[0078] A' / A and / or Z may be the same for both the first and second moiety (precursor). That is, the first anchorable component / anchoring component may or may not be the same as the second anchorable component / anchoring component. Likewise, the first linker group may or may not be the same as the second linker group.
[0079] A' may include an alkene group such as a diazonium salt, ethenyl or propenyl, or an alkene group such as ethinyl or methylethynyl.
[0080] In these embodiments, this means that A may include a bond, an alkylene group such as ethylene or propylene, or an alkenyl group such as ethenyl or propene.
[0081] Linker
[0082] Z is a linker group. Generally speaking, Z can have a wide variety of chemical properties. However, there are a few points to consider. First, silicon surfaces generally contain Si-H groups. Therefore, the linker group can be selected so as not to contain any groups that oxidize the silicon surface. For example, the linker group may not contain nucleophilic OH or NH groups, such as alcohols or primary or secondary amines. Second, as illustrated by the reaction diagram above, the typical method of attachment to the silicon surface is via free radical reactions, for example, through addition across unsaturated carbon-carbon bonds. This type of radical addition will generally generate free radicals at the carbon connected to the linker group. With this in mind, the linker group must be compatible with free radical reactions and capable of stabilizing free radicals on the connected atoms.
[0083] Linker groups may be compatible with free radical reactions if they do not contain any groups that would compete with anchorable groups in the reaction pathways specified above. For example, multiple ethylenyl groups within the linker group may compete with anchorable groups, resulting in less controlled surface decoration.
[0084] Of course, it is known that most functional groups will react with free radicals. However, the proper design of the linker group can mitigate side reactions.
[0085] The linker must be compatible with the reaction used for propagation of the polymer brush after anchoring to the Si-particle.
[0086] These design criteria still leave a wide range of options for Z.
[0087] For example, Z can be a bond. Alternatively, Z may include a functional group selected from arylene, alkylene, ester, ether, or amide.
[0088] Z can additionally be optionally substituted with a group such as a halogen. However, when using such a substituent, the relative reactivity of the halogen in free radical reactions must be taken into account, ensuring that the halogen is less reactive than the anchorable group and any polymerizable group that may be present.
[0089] Fluorine may be used, but if attached to a moiety that generates free radicals that are inherently less stable than those formed by an anchorable group or any polymerizable group, any one of chlorine, bromine, and iodine may be used. For example, aryl halides may be suitable for linker groups, whereas alkyl chlorides near unsaturated groups may form stabilized radicals, leading to side reactions that compete with the immobilization of the anchoring group and possibly subsequent polymerization reactions.
[0090] For example, Z is bonding, Z 1 , Z 2, -(CH2CH2O) 1-20 -(CH2) 1-2 -, Z 3 -C(O)OZ 3 , Z 3 -C(O)NH-Z 3 , Z 3 -C(O)NMe-Z 3 , or Z 3 -OZ 3 It can be selected from, where Z 1 is C1-C arbitrarily substituted with F 10 - Represents an alkylene, and Z 2 represents phenylene or naphthylene optionally substituted with F or Cl, and Z 3 is Z 1 or Z 2 It represents.
[0091] In some cases, Z is combined, Z 1 , Z 2 , or -(CH2CH2O) 1-20 -(CH2) 1-2 - can be selected from, where Z 1 is C1-C arbitrarily substituted with F 10 - Represents an alkylene, and Z 2 represents phenylene or naphthylene optionally substituted with F or Cl.
[0092] In some cases, Z is combined, Z 1 , or Z 2 It can be selected from, where Z 1 is C1-C arbitrarily substituted with F 10 - Represents an alkylene, and Z 2 represents phenylene or naphthylene optionally substituted with F.
[0093] In some cases, Z is combined or Z 2 It can be selected from, where Z 2 represents phenylene optionally substituted with F.
[0094] In some cases, Z can represent a bond.
[0095] Functional group
[0096] A' / A and / or Z may be the same for both the first and second moiety (precursor), but the groups may generally be terminated with different functional groups. The first moiety may be terminated with one or more first functional groups, whereas the second moiety may be terminated with one or more second functional groups.
[0097] The design criteria for functional groups generally follow the same principles as those for linker groups, that is, functional groups can be compatible with reactions that result in the anchorable group being immobilized on the surface when forming an anchoring group.
[0098] Functional groups are generally located on the surface of decorated Si particles, which means they can have a more significant influence on the surface properties of the particles.
[0099] The first moiety may contain a first functional group, which may be a polymerization initiator.
[0100] "Polymerization initiator" refers to a group including a radical stabilizer and a leaving group.
[0101] The first functional group may be a polymerization initiator including a radical stabilizer and a leaving group.
[0102] A radical stabilizer can be a mechanism that stabilizes radicals. Generally, radicals can be stabilized through superconjugation or resonance.
[0103] The radical stabilizer may include a carbon atom that can be directly bonded to the leaving group. The removal of the leaving group generally results in the formation of a radical. Therefore, the carbon atom that can be directly bonded to the leaving group will be the carbon from which the radical is formed.
[0104] The carbon may be highly substituted to ensure sufficient radical stabilization. For example, the carbon may be a tertiary carbon. One of the substituents on the carbon is a linker group bonded to an anchorable / anchoring component. The remaining substituent(s) may be alkyls, for example, methyl, ethyl, propyl, or butyl. Alternatively, one or more of the substituents may include lone pairs of electrons that increase radical stabilization. For example, the substituents may include functional groups such as ethers, esters, and amides. Alternatively, one or more of the substituents may include unsaturated moiety, such as phenylene or naphthalene, which stabilizes the radical through resonance.
[0105] Alternatively, the carbon may be a secondary carbon, i.e., a carbon bonded to a substituent selected from substituents having a leaving group and a lone pair of electrons or unsaturated substituents. The substituent is additionally bonded to a linker group bonded to an anchorable / anchoring component.
[0106] Nearby lone pairs of electrons increase radical stability. Exemplary substituents having lone pairs of electrons include functional groups such as ethers, esters, and amides.
[0107] The above secondary carbon may be located near an unsaturated moiety, such as a phenylene or naphthalene group, to enable radical stabilization through resonance. Upon radical formation, this will result in the formation of a benzyl radical. The above phenylene or naphthalene group may also be bonded to a linker group.
[0108] A leaving group is an atom or atomic group that is separated from the substrate during a reaction, particularly during a polymerization reaction to form a brush polymer as described herein. Any leaving group known to those skilled in the art may be suitable. Typical leaving groups include halides and pseudohalides.
[0109] Therefore, the functional group of the first moiety can be represented as Rad-LG, where Rad may be a radical-stabilizing moiety covalently bonded to the remainder of the first moiety (e.g., covalently bonded to Z), and LG is a leaving group.
[0110] In some cases, Rad is -(C6(R Rad2 )4)C*(R Rad1 )2, -(C 10 (R Rad2 )6)C*(R Rad1 )2-, -C*(R Rad3 )2, -OC(O)C*(R Rad1 )2, -NR Rad1 C(O)C*(R Rad1 )2, or -OC*(R Rad1 It can be selected from )2, where C* represents the carbon covalently bonded to LG, and each R Rad1 represents independently H or C1-C4-alkyl, and each R Rad2 is independently H, F, Cl, R Rad3 , NO2, -OR Rad3 , -C(O)OR Rad3 , or C(O)N(R Rad1 Representing )2, and each R Rad3 It independently represents a C1-C4-alkyl group.
[0111] In some cases, Rad is -(C6(R Rad2 )4)C*(R Rad1 )2, -(C 10 (R Rad2 )6)C*(R Rad1 )2-, C*(R Rad3 )2, -OC(O)C*(R Rad1 )2, or -NR Rad1 C(O)C*(R Rad1 It can be selected from )2.
[0112] In some cases, Rad is -(C6(R Rad2 )4)C*(R Rad1 )2, -OC(O)C*(R Rad1 )2, or -NRRad1 C(O)C*(R Rad1 It can be selected from )2.
[0113] In some cases, Rad is -(C6(R Rad2 )4)C*(R Rad1 It can be selected from )2.
[0114] In some cases, each R Rad1 It can independently represent H or methyl.
[0115] In some cases, R Rad1 It can represent H.
[0116] In some cases, each R Rad2 is independently H, F, Cl, R Rad3 , or -OR Rad3 It can represent.
[0117] In some cases, each R Rad2 is independently H, R Rad3 , or -OR Rad3 It can represent.
[0118] In some cases, each R Rad2 is independently H or R Rad3 It can represent.
[0119] In some cases, R Rad2 can represent H.
[0120] In some cases, R Rad3 can represent methyl.
[0121] Rad, R specified above Rad1 , R Rad2 , and R Rad3 The elements of can be combined in any combination.
[0122] For example, Rad is appropriately -(C6(R Rad2 )4)C*(R Rad1 )2, -(C 10 (R Rad2 )6)C*(R Rad1 )2-, -C*(R Rad3)2, -OC(O)C*(R Rad1 )2, or -NR Rad1 C(O)C*(R Rad1 It can be selected from )2, where C* represents the carbon attached to LG, and each R Rad1 represents independently H or methyl, and each R Rad2 is independently H or R Rad3 Represents, and R Rad3 represents methyl.
[0123] In some cases, Rad is -(C6(R Rad2 )4)C*(R Rad1 )2, -(C 10 (R Rad2 )6)C*(R Rad1 )2-, -C*(R Rad3 )2, -OC(O)C*(R Rad1 )2, or -NR Rad1 C(O)C*(R Rad1 It can be selected from )2, where C* represents the carbon attached to LG, and each R Rad1 represents independently H or methyl, and each R Rad2 is independently H, F, Cl, R Rad3 , NO2, -OR Rad3 , -C(O)OR Rad3 , or C(O)N(R Rad1 Represents )2, and R Rad3 represents methyl.
[0124] In some cases, Rad is -(C6H4)C*(R Rad1 )2, -(C 10 H6)C*(R Rad1 )2-, C*(R Rad3 It can be selected from )2, where C* represents the carbon attached to LG, and R Rad1 represents H or methyl, and R Rad3 represents methyl.
[0125] In some cases, Rad is -(C6H4)C*H2 or -(C 10H6)C*(H)2- can be selected from.
[0126] In some cases, Rad can represent -(C6H4)C*H2.
[0127] An exemplary leaving group (LG) may be selected from chloride, bromide, iodide, tosylate (toluenesulfonate), triflate (trifluoromethanesulfonate), or mesylate (methanesulfonate).
[0128] The first moiety (precursor) may include a leaving group (LG) selected from chloride, bromide, or iodide. This leaving group may be combined with any of the Rad groups shown above.
[0129] The first moiety may include one or more sites for polymerization. For example, the first moiety may include two polymerization initiators. An exemplary first moiety precursor includes 4-vinylbenzyl chloride.
[0130] The second moiety (precursor) may include one or more functional groups (FG). The functional group may be selected to act as a leaving group under conditions suitable for removing the leaving group(s) of the first moiety, thereby making it unsuitable for initiating polymerization. The presence of one or more functional groups within the second moiety (precursor) allows for the fine-tuning of the properties of the composite Si-particles. The second moiety can alter various different properties. For example, the second moiety may impart hydrophobic, hydrophilic, ionic, H-bonding, acidic, and / or basic properties.
[0131] The second moiety (precursor) may include one or more functional groups. For example, suitable functional groups may be selected from H, alkyl, aryl, carboxylic acid esters, carboxylic acid amides, nitriles, fluorides, or ethers.
[0132] In some cases, the second moiety (precursor) may include one or more functional groups selected from H, alkyl, aryl, carboxylic acid esters, nitriles, fluorine, or ethers.
[0133] The second moiety (precursor) may contain only one functional group. Alternatively, two or more functional groups may exist within the second moiety (precursor).
[0134] Carboxylic acid esters are compatible with anchorable / anchoring moiety and can acidify the surface layer by hydrolyzing the anchoring moiety after immobilization to produce carboxylic acid.
[0135] Therefore, the functional group of the second moiety can be expressed as follows: FG is -R FG1 , -C6(R FG2 )5, -C 10 (R FG2 )7, -C(O)OR FG3 , -C(O)N(R FG1 )2, -OC(O)-R FG1 , -N(R FG1 )-C(O)-R FG1 , CN, -(CH2) 14 -O-CH2-R FG1 , -(CH2CH2O) 120 -(CH2) 0-1 It represents CH3 or F, where each R FG1 is independently H or C 1-4 - Represents an alkyl group, and each R FG2 is independently H, F, Cl, R FG3 , NO2, -OR FG3 , -C(O)OR FG3 , or C(O)N(R FG1 Represents )2, and R FG3 is C 1-4 - Represents an alkyl group.
[0136] In some cases, FG is R FG1 , -C6(R FG2 )5, -C 10 (R FG2)7, -C(O)OR FG3 , -OC(O)-R FG1 , CN, -(CH2) 1-4 -O-CH2-R FG1 , -(CH2CH2O) 1-20 -(CH2) 0-1 It can represent CH3 or F.
[0137] In some cases, FG is R FG1 , -C6(R FG2 )5, -C(O)OR FG3 , CN, -(CH2CH2O) 1-20 -(CH2) 0-1 It can represent CH3 or F.
[0138] In some cases, FG is R FG1 , -C6(R FG2 )5, -C(O)OR FG3 , CN, or -(CH2CH2O) 1-20 -(CH2) 0-1 It can represent CH3.
[0139] In some cases, FG is H, -C6(R FG2 )5, -C(O)OR FG3 , or can represent CN.
[0140] In some cases, FG is H, -C6H5, -C6F5, -C(O)OR FG3 , or can represent CN.
[0141] In some cases, FG is H, -C6H5, -C6F5, -C(O)OR FG3 , or can represent CN, where R FG3 represents CH3 or tertiary-butyl.
[0142] In some cases, FG is H, -C6F5, -C(O)OR FG3 , or can represent CN, where R FG3 represents tertiary-butyl.
[0143] In some cases, each R FG1It can independently represent H or methyl.
[0144] In some cases, R FG1 It can represent H.
[0145] In some cases, each R FG2 is independently H, F, Cl, R FG3 , or -OR FG3 It can represent.
[0146] In some cases, each R FG2 is independently H, F, R FG3 , or -OR FG3 It can represent.
[0147] In some cases, each R FG2 It can independently represent H, F, or CH3.
[0148] In some cases, R FG2 can represent H or F.
[0149] FG, R FG1 , R FG2 , and R FG3 These above embodiments of can be combined in any combination.
[0150] An exemplary second moiety precursor may be selected from tertiary-butyl acrylate, styrene, pentafluorostyrene, or acrylonitrile. For example, the second moiety precursor may be selected from tertiary-butyl acrylate, styrene, or pentafluorostyrene.
[0151] For various grafting methods, the immobilization rate of the moiety precursor can be accelerated by the use of initiator species consumed early in the reaction or by the application of catalytic species, such as transition metal complexes or diazonium salts, as described above. In such cases, additional control can be achieved during the grafting step of the base layer by modifying the properties and loading of the initiator and / or catalyst.
[0152] Composite particles
[0153] Composite particles (i.e., silicon particles decorated with first and second moieties) may have a slightly larger diameter than undecorated silicon particles. The difference in size may generally not be measurable, for example, C as a linker 10 This is because decorating particles with relatively large moieties containing alkylene chains can increase the particle diameter by only a few nanometers, while the width of the initial particle size distribution (PSD) is only tens of nm to a maximum of about 100 nm, and typical non-spherical particle shapes also contribute to this wide PSD. Overall, this decoration may have a negligible effect on the D50 value of the particles and would be difficult to measure reliably using methods such as dynamic light scattering.
[0154] In one embodiment of the present disclosure, the composite particle has an average diameter (D50) of about 10 nm to about 500 nm, for example, about 25 nm to about 300 nm, for example, about 50 nm to about 200 nm, for example, about 75 nm to about 150 nm. The average diameter (D50) may be particularly about 50 nm, about 75 nm, about 100 nm, about 125 nm, about 150 nm, about 175 nm, or about 200 nm.
[0155] To form composite particles, first and second moieties are immobilized on the surface of Si particles to form decorated particles.
[0156] Accordingly, in one aspect of the present disclosure, a method for forming a composite particle is provided, the method comprising: providing a silicon particle, a first moiety precursor comprising a first anchorable component and a first functional group (e.g., a polymerization initiator), and a second moiety precursor comprising a second anchorable component and a second functional group; and decorating the silicon particle by reacting the first anchorable component of the first moiety precursor to form a first anchoring component of the first moiety and reacting the second anchorable component of the second moiety precursor to form a second anchoring component of the second moiety, wherein the first anchoring component and the second anchoring component are covalently bonded to the silicon particle.
[0157] In some cases, silicon particles contain Si-H groups on the surface of the particles. Providing silicon particles (i.e., step ai) may include the step of exposing silicon particles to HF to form Si-H moiety on at least a portion of the surface of the silicon particles.
[0158] Generally, the first and second moiety precursors may be provided as one or more mixtures with one or more solvents.
[0159] The solvent can be selected to be compatible with the reaction that converts the anchorable component into the anchoring component. Additionally, the solvent may have low reactivity toward the silicon surface. The solvent may be ethers, cyclic ethers, aromatic solvents, and similar substances, such as acetonitrile, tetrahydrofuran, ethyl acetate, and methyl 3rd- The solvent includes, but is not limited to, those selected from butyl ether, xylene, toluene, dioxane, or hexane. In some cases, the solvent is selected from tetrahydrofuran, xylene, toluene, or dioxane. Additionally, anhydrous and deoxygenated solvents may be applied to prevent oxidation of the Si surface by residual moisture and oxygen.
[0160] The reaction resulting in the decoration of silicon particles (i.e., the reaction in which the first and / or second anchorable component reacts to form the first and / or second anchoring component) may be a diazonium immobilization reaction or hydrosilylation. Hydrosilylation may be suitable in some cases.
[0161] The first and second moiety precursors can generally be immobilized on the surface of the Si particles at the same stage. This may also be referred to as co-immobilization.
[0162] When the first and second moiety precursors are immobilized simultaneously, they can be allowed to react until the surface of the Si-particle is completely covered. This means that the reaction between the moiety precursor and the surface of the Si-particle stops, leaving no space for additional moiety to attach. This does not necessarily mean that all hydrides on the Si-surface (e.g., Si-H moiety) are exchanged for the first or second moiety. More likely, it means that the steric hindrance of the bonded moiety prevents access to the remaining hydrides on the surface. The remaining hydrides on the surface may subsequently oxidize, forming a Si-OH moiety on the surface. Surprisingly, the decorative layer of the immobilized species passivates the silicon surface, meaning that Si-H bonds can be maintained even under various conditions where they would otherwise oxidize the surface.
[0163] Considering that surface covering can serve a protective role, a complete reaction between the surface of the Si particles and the first and second moiety precursors may be a suitable choice. For example, it is known that oxygen and moisture cause degradation of Si particles (particularly, untreated and H-terminated silicon). Degradation caused by oxygen and moisture can be reduced by decorating the particles with first and second moiety.
[0164] The total number of moieties immobilized on Si particles can vary depending on various factors such as reaction time, temperature, and the concentration of species grafted onto the substrate. Additionally, this depends on the stereostructure of the species immobilized on the surface. Compared to the immobilization of small moieties, the immobilization of bulky and stereotactically disruptive moieties can result in a lower maximum total number of immobilized moieties than can be achieved for smaller moieties.
[0165] A schematic diagram of a composite silicon particle containing surface decorations of immobilized first and second moieties is shown in FIG. 1a. The relative ratio of the first and second moieties can be used to control the surface properties of the particle. For example, decorating the particle with multiple moieties can control the surface properties of the particle, such as its solubility, dispersibility, adhesion, hydrophobicity, hydrophilicity, acid / base properties such as pI, and its reactivity, electronic and ion conductivity. Additionally, the relative amount of the first moieties having polymerizable groups can influence the properties of the polymer brush formed on the decorated particle.
[0166] Since the surface reactivity of composite particles can be controlled by the ratio of first and second moieties, the present disclosure provides a methodology for decorating Si particles to obtain specific properties. In particular, by decorating the particles with at least two different moieties (i.e., first and second moieties), control of the grafting density during polymer brush formation can be obtained. By varying the ratio between the first and second moieties, a higher or lower number of initiation sites for subsequent polymer brush formation can be obtained. This, in turn, can affect the formation of the polymer brush.
[0167] For example, the ratio of the first moiety precursor to the second moiety precursor used to decorate the Si-particle may be 2:98 to 98:2, e.g., 5:95 to 95:5, e.g., 1:9 to 9:1, e.g., 1:6 to 6:1, e.g., 1:3 to 3:1, e.g., 1:2 to 2:1, e.g., 2:3 to 3:2.
[0168] In some cases, the ratio of the first moiety precursor to the second moiety precursor used to decorate the Si-particle may be 1:9 to 1:1, for example 1:6 to 2:3, for example 1:4 to 2:3, for example 1:3 to 1:2.
[0169] In some cases, the ratio of the first moiety precursor to the second moiety precursor used to decorate the Si-particle may be 1:1 to 9:1, for example 3:2 to 6:1, for example 4:1 to 3:2, for example 3:1 to 2:1.
[0170] The reactivity of the first moiety precursor and the second moiety precursor to the Si-particle surface may differ. Therefore, a mixture in which the ratio of the first moiety precursor to the second moiety precursor is 1:1 may not necessarily result in a composite particle in which the first moiety and the second moiety are combined in a 1:1 ratio.
[0171] While we do not wish to be bound by theory, it is believed that differences in reactivity may be caused by different stereochemical and / or electronic properties of moiety precursors. For example, relatively larger moiety precursors may exhibit lower reactivity compared to relatively smaller ones. Likewise, it is generally known that alkynes exhibit higher reactivity than their corresponding alkenes in hydrosilylation reactions.
[0172] To determine the ratio between the first and second moieties constituting the decoration of the composite particle, the relative density of each component can be obtained. The relative density is used to describe the amount of a specific moiety immobilized on the Si particle relative to the maximum obtainable amount of the corresponding moiety that can be immobilized on the Si particle. The maximum obtainable amount corresponds to the amount of immobilized moieties when a single type of moiety reacts with the surface of the Si particle in excess.
[0173] The amount of moiety for Si particles can be determined using Fourier Transform Infrared Spectroscopy (FTIR). Since different functional groups provide different peaks in the infrared spectrum (IR spectrum), these peaks can be used to determine the relative amount of moiety upon integration.
[0174] After determining the relative density, the relative surface stoichiometry can be calculated. The relative surface stoichiometry is the relative grafting density of one of the grafted species ( ) and the sum of all relative grafting densities( It is the ratio of ):
[0175]
[0176] The relative surface stoichiometry of the first moiety for silicon particles is at least 0.5%, e.g., at least 1%, e.g., 5%, e.g., at least 10%, e.g., at least 15%, e.g., at least 20%, e.g., at least 25%, e.g., at least 30%, e.g., at least 40%, e.g., at least 50%, e.g., at least 60%, e.g., at least 75%, e.g., at least 85%, e.g., at least 90%.
[0177] The relative surface stoichiometry of the second moiety for silicon particles is at least 5%, e.g., at least 10%, e.g., at least 15%, e.g., at least 20%, e.g., at least 25%, e.g., at least 30%, e.g., at least 40%, e.g., at least 50%, e.g., at least 60%, e.g., at least 75%, e.g., at least 85%, e.g., at least 90%.
[0178] Relative surface stoichiometry can be fitted to the composition of the reaction mixture and thus determine the relative rate constant of the reaction with respect to the surface. This relates to the study by Faucheux et al., which describes two types of grafting with different rate constants on surfaces having reactive sites consumed during molecular grafting (reference [" Langmuir This can be achieved using an equation based on [see 2006, 22, 1, 153-162]:
[0179]
[0180] Here, n1 and n2 are species 1 and 2. Relative grafting density It represents, and therefore is species 2's Relative surface stoichiometry k1 and k2 are the rate constants of the reaction on the surfaces of species 1 and 2, and c2 is the fraction of reactive species 2 in the reaction mixture.
[0181] Generally, only one type of first moiety precursor and one type of second moiety precursor are immobilized on the surface to form a composite particle decorated with only one type of first moiety and one type of second moiety.
[0182] However, for various reasons, it may be beneficial to use more than one first moiety and / or more than one second moiety when decorating Si particles.
[0183] The first moiety may also be referred to as a polymerization initiation species. This implies that polymer chains can be grafted from the first moiety. For example, the first moiety may be an SI-ATRP (surface-initiated atom transfer radical polymerization) initiator, an SI-NMP (surface-initiated nitroxide-mediated polymerization) initiator, an SI-PIMP (surface-initiated photoinitiator-mediated polymerization) initiator, an SI-A(R)GET (surface-initiated photoinitiator-mediated polymerization) initiator, a SET-LRP (single electron transfer living radical polymerization) initiator, or a SARA ATRP (supplementary activator and reducing agent atom transfer radical polymerization) initiator. The introduction of more than one type of polymerization initiation species opens up the possibility of performing two different polymerizations. For example, ATRP-like polymerization can be performed first from an ATRP initiator, and then a different polymer structure can be grown from a RAFT initiator under RAFT conditions.
[0184] In some cases, the Si particles can be decorated with more than one type of first moiety.
[0185] Likewise, decorating Si particles with more than one second moiety can provide an opportunity to improve different surface properties of the Si particles, such as pI, hydrophobicity, hydrophilicity, dispersibility, adhesion, and electronic and ion conductivity.
[0186] In some cases, Si particles can be decorated with more than one type of second moiety.
[0187] Polymer brush composite particles
[0188] After the Si-core is decorated with first and second moieties and the first moiety forms a composite particle having a polymerization initiator, a polymer brush can be formed from the first moiety. Refer to arrow 2 in FIG. 1b.
[0189] Polymer brushes can also be referred to as surface polymers.
[0190] "Surface polymer" describes a polymer structure having polymer chains chemically bonded to the surface at one end through covalent bonds.
[0191] Two methods known to those skilled in the art can be used to achieve this polymer structure: the "grafting to" approach and the "grafting from" approach. In the "grafting to" approach, the polymer is prepared in solution and then deposited onto the surface, as one of the chain ends of the pre-prepared polymer is designed to have some affinity for the surface of interest. Upon contact with the surface of interest, the polymer self-assembles onto the surface to form a surface-bonded polymer. In the "grafting from" approach, a small molecule capable of acting as a polymerization initiator is covalently bonded to the surface of interest in the pre-polymerization stage. Subsequently, polymerization is initiated via the polymerization initiator. Thus, the surface polymer is grafted from the surface.
[0192] "Grafting to" is a method of attaching polymer chains to a surface. The polymer chains are covalently bonded to the surface at one chain end. The method involves a step of pre-forming a polymer in solution, wherein the polymer possesses reactive chain end groups. In solution, these polymers are not yet attached to the surface. The reactive end groups can react with suitable reactive groups on the corresponding surface. Typically, the reactive groups are deposited on the surface or pre-formed in other ways. The pre-formed polymer is introduced into the solution, where the shape of the individual polymer chains is determined by solvent interactions and energy. Generally, the chains will take on a coiled form to maximize entropy. This form is maintained when the reactive chain ends react with the reactive groups on the surface. The surface area occupied by grafting this polymer coil is generally much larger than the surface area occupied by the reactive surface groups; therefore, nearby reactive surface groups are blocked from reacting by the polymer coil. Theoretically, if the chains were grafted onto the surface in an elongated linear form, a much higher polymer grafting density could be obtained. However, such a form is not easily achievable for polymers in solution, considering the entropy-favorable coiled shape that chains take in solution. Straight and linear polymer forms are highly entropy-unfavorable and are therefore not generally observed in polymers in solution. However, surface polymer decorations containing more linear polymer chains attached to the surface at a much higher density can be obtained using the "grafting from" methodology described below.
[0193] The "grafting to" approach enables a simple manufacturing procedure in that polymers can be prepared using conventional polymerization methods and stored before initiating the self-assembly process; however, the "grafting to" approach lacks the ability to form high-density surface-bonded polymer structures. The main problem is that when pre-fabricated polymer chains self-assemble on a surface, the self-assembly process is halted by steric repulsion between them.
[0194] The "grafting from" approach enables the formation of high-density surface-bonded polymer structures because small molecules can form a layer packed much more densely on the surface (compared to large polymer molecules). Consequently, surface-bonded polymer structures formed by the "grafting from" approach result in much higher densities. Furthermore, since the "grafting from" approach enables high-density surface-bonded polymer structures, brush-like structures can be achieved, hence the name "polymer brush." In such structures, polymers are forced to stretch and stand upright as a result of steric repulsion between nearby polymers, creating a unique structure recognized by those skilled in the art as a "polymer brush" structure. On the surface, these structures are tethered / attached at one end to the surface, typically a solid or semi-solid surface, usually attached by covalent bonds, distinguishing them from polymers formed in solution and subsequently deposited on the surface.
[0195] In the "grafting from" approach, surface polymer growth (surface polymer chain propagation, chain extension by monomer units) is initiated from an initiator-functionalized surface, using controlled / "living" polymerization techniques, particularly radical polymerization.
[0196] Different polymerization technologies have enabled strict molecular control and the specific design and synthesis of surface polymers with desired properties. In particular, surface polymers can be viewed as nanoscale "building blocks" with a wide range of applications, from redox activity to biocompatibility and surface modification; furthermore, due to the flexibility of surface polymers, highly customized thin films of surface polymers can be produced regarding chemical composition, thickness, grafting density, and structure.
[0197] When forming a surface polymer, a surface containing a polymerization initiator is brought into contact with a suitable monomer, catalyst, ligand, and optionally a solvent, or with a suitable monomer, catalyst, ligand, oxygen scavenger, and optionally a solvent, thereby allowing the surface polymer to be formed using specific reaction conditions. The polymerization initiator and monomer are selected to suit the purpose and properties of the surface polymer to be formed. The surface polymer can also be formed as a layer of the surface polymer by repeating the polymer structure, for example, using another starting monomer (coblock polymer).
[0198] Several methods for forming surface polymers are known, including SI-ATRP (Surface-Initiated Atom Transfer Radical Polymerization), SI-RAFT (Surface-Initiated Reversible Addition-Fragmentation Chain Transfer), SI-NMP (Surface-Initiated Nitroxide-Mediated Polymerization), SI-PIMP (Surface-Initiated Photoinitiator-Mediated Polymerization), and SI-A(R)GET (Surface-Initiated Activator (Regenerated) by Electron Transfer) ATRP. A review is provided in the literature [Chem. Rev. 2009, 109, 5437-5527]. Other approaches include SET-LRP (Single Electron Transfer Living Radical Polymerization), SARA ATRP (Supplementary Activator and Reducing Agent Atom Transfer Radical Polymerization), and (ARGET) ATRP ((Activator Regenerated by Electron Transfer) Atom Transfer Radical Polymerization). Monomers, catalysts, ligands, and solvents are required for the polymerization chain to proceed. (ARGET) In ATRP and SET-LRP polymerization, some reactions activate the catalyst to promote polymerization, while simultaneously, other reactions deactivate the catalyst to inhibit polymerization. SARA-ATRP and SET-LRP are described, for example, at https: / / www.cmu.edu / maty / atrp-how / procedures-for-initiation-of-ATRP / SARA-ATRP-or-SET-LRP.html. From WO 2019 / 196999 A1, the entirety of which is incorporated herein by reference, an alternative oxygen-tolerant method for forming surface polymers is disclosed. The catalyst system used is halogen-free because a complex is formed between the transition metal and the ligand. The main advantage of the disclosed catalyst system is that the complex formed between the transition metal and the ligand is inactive (i.e., unusable for initiating monomer polymerization) and stable (oxygen-insensitive), but the system can be activated by an oxygen scavenger "when necessary" to reduce the transition metal of the transition metal-ligand complex, thereby initiating the polymerization and propagation of the surface polymer.All of these methods can be used to propagate a polymer brush from an initiator site of a silicon particle and to form a decorated silicon particle as disclosed herein.
[0199] To propagate polymer brushes, the polymerization reaction composition may include a monomer, a catalyst, a ligand, a catalyst activator, and optionally a solvent. In some cases, the monomer may serve as the solvent.
[0200] Examples of suitable catalyst activators include, but are not limited to, sodium ascorbate, ascorbic acid, hydrazine, hydrazine hydrate, sodium hypophosphite, glucose, tin 2-ethylhexanoate, sodium phenoxide, sodium dithionite, mixtures of iron powder and sodium chloride, bicarbonates, citric acid, and pyrogallic acid. The activator for the catalyst (e.g., an oxygen scavenger) may be used in excess of the transition metal. The excess may be, for example, 1 to 250 times.
[0201] Examples of suitable catalysts may be based on transition metals (defined in the periodic table of elements). Suitable examples of transition metals include compounds derived from copper (Cu), iron (Fe), and ruthenium (Ru). In some cases, the catalyst may be based on transition metals derived from Cu and / or Fe species. Specific examples of such catalysts include Cu2O, CuO, CuCl, CuCl2, CuBr, CuBr2, FeO, Fe2O3, Fe2O4, FeCl2 and FeCl3, and combinations thereof. In one embodiment, the catalyst is based on Cu. The catalyst concentration in the polymerization reaction composition may be in the range of 0.001 to 1 mM. The concentration of Cu in the polymerization reaction composition may be in the range of 0.02 to 0.32 mM, for example, 0.02 mM, 0.04 mM, 0.08 mM, 0.16 mM, or 0.32 mM.
[0202] According to the method disclosed in this specification, a catalyst activator may be added multiple times during surface polymer formation to control polymer brush formation over time.
[0203] At least one ligand may be included in the polymerization reaction composition. The ligand may be a nitrogen-containing compound. Non-limiting examples of such nitrogen-containing compounds include di-, tri-, or tetra-coordinated amine ligands of aliphatic and / or aromatic nature (containing two, three, or four amine substituents). In particular, such ligands include N,N,N',N",N" Includes 2-pentamethyldiethylene-triamine (PMDETA), tris-[2-(dimethyl-amino)-ethyl]-amine (Me6TREN), tris(2-amino-ethyl)-amine (TREN), tris(2-pyridyl-methyl)-amine (TPMA), and 2,2'-bipyridyl (BiPy), and combinations thereof. The amount of ligand in the polymerization reaction composition is defined as a ratio to the catalyst concentration in the polymerization reaction composition. The ratio of ligand to catalyst in the polymerization reaction composition is in the range of 0.001:1 to 1000:1. The ratio of ligand to catalyst in the polymerization reaction composition may be in the range of 0.005:1 to 100:1, for example, 0.13:1, 0.5:1, 1.0:1, 2.0:1, 3.5:1, 7.5:1, or 12:1. Generally, an excess amount of ligand can be used compared to the amount of catalyst.
[0204] The monomer for forming the surface polymer may be any desired monomer for the final product. Non-limiting examples of suitable monomer types include anionic, cationic, diionic, protic, and aprotic monomers, as well as acrylates; methacrylates; halogen-substituted alkenes; acrylamide; methacrylamide; and styrene, and mixtures thereof.
[0205] A typical monomer structure includes a polymerizable portion (alkenyl group), which, in certain embodiments, is connected to a functional group responsible for the specific functionality of the specific monomer (e.g., adhesion, permeability, electrical and ion conductivity) through specific linker chemistry.
[0206] In the case of acrylate monomers, non-limiting examples of functional moiety include, but are not limited to, alkyl groups, sulfonates, fluorosulfonates, carboxylates, metal carboxylates, ethers, poly(ether) groups, bis(sulfonyl)amides, fluorinated sulfonates, perfluoroalkyl carboxylates, borates, fluorinated borates, borate ester derivatives, tetraphenylborate, bis(trifluoro-methane)-sulfonimide, trilimide and derivatives thereof, alkyl halides, and mono-, di-, and tri-alkoxysilanes.
[0207] The polymerizable portion and the functional portion of the monomer may be connected by a linker moiety in certain embodiments. Non-limiting examples of suitable linker chemistry include, but are not limited to, alkyl chains, esters, ethers, poly(ethers), amines, amides, aryls, and any combination(s) thereof.
[0208] Non-limiting examples of suitable acrylate monomers containing alkyl linkers include C1-C 16 - Alkyl, such as methyl acrylate, ethyl acrylate, tert-butyl acrylate, and lauryl acrylate, are included but not limited thereto.
[0209] Non-limiting examples of monomers using ether and poly(ether) linker chemistry include, but are not limited to, poly(ethylene glycol) methyl ether acrylate and poly(ethylene glycol) acrylate.
[0210] Non-limiting examples of monomers without linker chemistry include, but are not limited to, acrylic acid; lithium acrylate; and sodium acrylate.
[0211] For methacrylate monomers, non-limiting examples of suitable functional moiety include, but are not limited to, carboxylic acids, metal carboxylates, esters, alkyl alcohols, oxyranes, linear and branched alkyl groups, sulfonates, fluorosulfonates, bis(sulfonyl)amides, fluorinated sulfonates, perfluoroalkyl carboxylates, borates, fluorinated borates, borate ester derivatives, tetraphenylborate, bis(tri-fluoro-methane)sulfonimide, trilimide, and derivatives thereof, alkyl halides, and mono, di, and tri-alkoxysilanes.
[0212] Non-limiting examples of linker chemistry include alkyl chains (e.g., C1-C 16 -alkyl), esters, ethers, poly(ethers), amines, amides, aryls, and any combination(s) thereof are included but not limited thereto.
[0213] Non-limiting examples of methacrylate monomers include methacrylic acid, lithium methacrylate, sodium methacrylate, methyl methacrylate (MMA), potassium 3-sulfopropyl methacrylate, 2-hydroxyethyl methacrylate (HEMA), glycidyl methacrylate (GMA), ethyl methacrylate, n -Butyl methacrylate, 3rd- Butyl methacrylate and lauryl methacrylate are included, but not limited to.
[0214] Suitable non-limiting examples of halogen-substituted alkene monomers include, but are not limited to, vinyl chloride, vinylidene difluoride, tetrafluoroethylene, chlorotrifluoroethylene, and hexafluoropropylene.
[0215] Non-limiting examples of suitable acrylamide monomers include acrylamide, N -iso-propylacrylamide, N -3-butylacrylamide, and N- Includes, but is not limited to, hydroxyethyl acrylamide.
[0216] Non-limiting examples of suitable methacrylamide monomers include N -Iso-propylmethacrylamide, methacrylamide, N -ter-butyl methacrylate, and N - Includes, but is not limited to, hydroxyethyl methacrylamide.
[0217] Non-limiting examples of suitable styrene monomers include styrene; 4-methylstyrene, 2,3,4,5,6-pentafluorostyrene, p - Divinylbenzene, 4-chlorostyrene, sodium 4-vinylbenzenesulfonate, lithium 4-vinylbenzenesulfonate, and 4-vinylphenyl 1,1,2,2,3,3,4,4,4-nonafluorobutane-1-sulfonate are included, but not limited to.
[0218] Monomer(s) may be selected to provide compatibility / adhesion / elasticity suitable for specific applications. Monomer(s) may also be selected to improve or reduce electrical and / or ionic conductivity and / or permeability. Monomer(s) may be selected to improve the interfacial stability of the corresponding surface.
[0219] The polymer brush thickness can be 1–1,000 nm. The thickness of the polymer brush may vary depending on the specific intended application and may be 1–500, 1–250 nm, 5–100 nm, 120–250 nm, 10–80 nm, or 10–30 nm. It is generally impossible to accurately measure the thickness of the dried polymer layer. Instead, the surface polymer thickness can be estimated from DLS measurements of the suspended particles. Since the solvent can penetrate into the surface polymer and cause swelling, the results obtained may vary depending on the solvent used. Furthermore, the dispersibility / solubility of the particles will vary depending on the solvent, which means that direct comparison between particles with differently treated surfaces may not be possible. For illustrative purposes, particles decorated with a polymer brush have a D of about 50 nm to about 1.5 μm, e.g., about 150 nm to about 1.2 μm, e.g., about 200 nm to about 750 nm. [4,3] It can have a value of 50.
[0220] A polymer brush layer can be applied or formed by repeating the specific steps above to construct a block copolymer. The same or different monomers used to form the previous layer may be applied. Forming additional layers of the surface polymer can be repeated multiple times to obtain a more complex or thicker surface polymer. The surface polymer can also be formed using two or more different monomers grown from one or different types of initiators, thereby forming a random or mixed surface polymer, respectively. Thus, two or more functional groups (e.g., halogen atoms, hydroxyl groups, or amine groups) may be incorporated, resulting in the formation of a polymer brush having a unique set of combined characteristics unique to each individual monomer.
[0221] A polymer brush can be formed from a surface-immobilized initiator upon contact with a polymerization reaction composition comprising a ligand, a catalyst, a monomer, a catalyst activator, and a solvent.
[0222] The concentration of polymerization initiator species (first moiety) significantly affects polymer chain growth. Higher concentrations of these species can lead to the proximity of growing macroradics. This can result in recombination, which may prevent further polymer chain growth. The polymer chain loops formed as a result of recombination can be beneficial to the mechanical properties of the particles. Lower concentrations of polymerization initiator species can enable unrestricted polymer chain growth and facilitate the formation of extended polymer chains. These higher molecular weight polymer chains can increase the degree of entanglement, thereby improving the cohesion between individual particles.
[0223] At specific polymer initiator species densities between higher and lower concentrations, the growing polymer chains extend perpendicularly to the surface, forming a dense polymer layer with reduced permeability of various species through the polymer shell. Thus, the density of the first moiety bound to the composite particle can enable control over the formation of the polymer brush and the overall characteristics of the polymer brush composite particle.
[0224] The disclosure of this specification relates more to polymer brush composite particles.
[0225] The polymer brush composite particle may comprise a first moiety comprising a polymer moiety and a first anchoring component covalently bonded to at least a silicon core, and a silicon core decorated with a second moiety comprising a second anchoring component covalently bonded to the silicon core and one or more functional groups.
[0226] The linear polymer chains of the formed polymer brush may have an average length of about 2 repeating units to about 1,000 repeating units, for example, about 5 repeating units to about 750 repeating units, for example, about 10 repeating units to about 500 repeating units, for example, about 15 repeating units to about 100 repeating units, or about 20 repeating units to about 75 repeating units.
[0227] The polymer moiety is generally connected to the first moiety via a covalent bond to the radical-stabilizing moiety Rad, as follows: [Si]-AZ-Rad-[P], where [Si] is the silicon particle core, A is the anchoring component, Z is the linker group, Rad is the radical-stabilizing moiety, and [P] is the polymer chain.
[0228] The remainder of the decorated particle comprises the following moiety covalently bonded to the silicon particle core: [Si]-AZ-FG, and optionally [Si]-AZ-Rad-LG, where [Si] is the silicon particle core, A is the anchoring component, Z is the linker group, Rad is the radical stabilizing moiety, LG is the leaving group, and FG is the functional group, where [Si]-AZ-Rad-LG represents the residual amount of the first moiety that did not undergo polymerization to form the polymer brush.
[0229] For completeness, the composite particles prior to polymer brush formation can be represented as follows: [Si]-AZ-FG and [Si]-AZ-Rad-LG, where [Si] is the silicon particle core, A is the anchoring component, Z is the linker group, Rad is the radical stabilizing moiety, LG is the leaving group, and FG is the functional group.
[0230] Polymer brush composite particles are formed from composite particles by exchanging a polymer chain that propagates a leaving group of a first moiety through a polymerization reaction. Polymer brush propagation can be achieved by a method comprising the steps of: providing a composite particle comprising a first moiety having a first anchoring component and a polymerization initiator covalently bonded to at least a silicon core, and a silicon core decorated with a second moiety having a second anchoring component and one or more functional groups covalently bonded to the silicon core; forming a polymerization reaction composition comprising one or more polymerization catalysts and one or more monomers; and exposing the composite particles to the polymerization reaction composition.
[0231] As described in the disclosure of this specification, the step of exposing the composite particles to a polymerization reaction composition results in the propagation of polymer chains through a reaction with the polymerization initiator of the first moiety.
[0232] In some embodiments, the polymerization reaction composition may be formed from a polymerization composition comprising at least one dormant transition metal catalyst, an activator comprising an oxygen scavenger, and one or more monomers, wherein the one or more monomers may be provided as part of the polymerization composition, part of the activator, or as a separate composition.
[0233] Accordingly, in some cases, a method for forming polymer brush-decorated composite particles may include the steps of: providing a composite particle comprising a silicon core decorated with a first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to at least a silicon core, and a second moiety comprising a second anchoring component and one or more functional groups covalently bonded to the silicon core; providing a polymerization composition, an activator, and one or more monomers, wherein the polymerization composition comprises one or more dormant transition metal catalysts, the activator comprises one or more oxygen scavengers, and one or more monomers may be part of the polymerization composition, part of the activator, or a separate composition; and combining the polymerization composition, the activator, and one or more monomers to form a polymerization reaction composition; and exposing the composite particle to the polymerization reaction composition.
[0234] The monomer, catalyst, ligand, catalyst activator, and solvent and their amounts are described above.
[0235] The composite particle with the polymerization initiator immobilized thereon and the polymerization reaction composition can be maintained in contact with each other for a suitable period (residence time). The residence time includes, but is not limited to, 0.1 seconds to 5 hours. The residence time may vary depending particularly on the desired thickness and formation rate of the formed polymer brush.
[0236] Polymer brush formation can be performed at ambient temperature (room temperature) or with cooling or heating. Suitable temperatures are -20°C to 120°C, such as room temperature (about 20°C) to 120°C.
[0237] The residence time and temperature during the residence time can suitably be controlled by a computer. Other methods for controlling the residence time and temperature may be based on the conditions (bath conditions) and / or measurements of the compartment holding the polymerization reaction composition.
[0238] In particular, the chemical structure and functionality of non-initiating species in the basal layer influence the surface chemistry of the final material. The chemical properties and functionality of non-initiating species in the basal layer and the chemical properties and functionality of repeating units of the polymer brush may be similar or different from each other. This means that orthogonal chemical properties, such as hydrophobic and hydrophilic moiety, may exist simultaneously on the surface, with one type existing in the non-initiating portion of the basal layer and the other type(s) existing in the polymer brush portion of the structure.
[0239] When considering a polymer brush grown from a first moiety of composite particles, several different types may be included, such as block copolymers, polymers capable of reacting in subsequent steps like crosslinking, or the incorporation of other functional moiety that alters the polymer brush functionality. If the base layer consists of two different initiation species designed for different polymerization reactions, e.g., RAFT and ATRP, the two different types of polymers may be anchored to the surface to provide a hybrid polymer brush composite particle.
[0240] The composite particles can be decorated with one or more first moieties. The introduction of more than one type of initiator opens up the possibility of enabling the formation of mixed-species polymer brushes, for example, by first performing ATRP-like polymerization from an ATRP initiator of the base layer and then growing different polymer brush structures under RAFT conditions from a RAFT initiator. Additionally, the base layer can be chemically modified both before and after the polymerization step to introduce desired chemical structures and properties.
[0241] In the present disclosure, suitable solvents include alcohols such as methanol, ethanol, and isopropanol. Aprotic solvents such as dimethyl sulfoxide (DMSO), acetone, dimethyl-formamide, tetrahydrofuran, propylene carbonate, methylene carbonate, ethylene carbonate, ethyl lactate alcohol, and ionic liquids may also be used in the present method. In some embodiments, the solvent may be a mixture with water. In some cases, the solvent may be a mixture of water and alcohol.
[0242] In the method of the present disclosure, a polymer brush is formed on the surface of a Si-particle. A first moiety having a polymerization initiator is immobilized thereon on the surface. The first moiety acts as an initiator for a polymerization reaction.
[0243] After the polymer brush is formed, the functionalized particles are removed from the polymerization medium.
[0244] Brush polymers can be formed from one or more monomers. That is, brush polymers may contain one or more repeating units. For example, a brush polymer may be a block copolymer containing two different repeating units. To form a block copolymer, composite particles are first reacted with one type of monomer, and then the composite particles are reacted with another type of monomer. Another example is the formation of a random block copolymer, where two or more monomers are included in the polymerization reaction composition.
[0245] complex aggregates
[0246] When the surface of a particle is to be uniformly decorated with at least one type of first moiety and one type of second moiety, the particle can be completely dispersed in the reaction medium, whether it is a reaction medium used to decorate silicon particles or a polymerization reaction composition used to form a polymer brush on a composite particle.
[0247] Silicon particles and / or composite particles can be dispersed by various methods, such as vigorously stirring in a suitable solvent. Complete dispersion can be achieved by stirring the particles for a sufficient time, for example, at least 10 minutes, such as 1 hour to 24 hours, or generally 4 hours to 18 hours. Increasing the temperature can reduce the time required to achieve complete dispersion of the particles. If necessary, dispersion can be achieved by sonic stirring, such as using an ultrasonic processor or an ultrasonic horn.
[0248] In some embodiments, silicon particles and / or composite particles may not be completely dispersed when exposed to conditions that result in the decoration of the Si-core and / or the formation of polymer brushes. In other words, the silicon particles may be in the form of aggregates while being decorated. This may result in decorated aggregates having an inner surface that may have different surface characteristics from the functionalized outer surface. In some situations, the formation of such decorated aggregates may be desirable because the resulting aggregates may have a useful surface mixture that provides interesting properties. For example, an aggregate having at least a portion of an inner surface composed of a functionalized outer surface and unreacted silicon (e.g., silicon hydride or silicon oxide) may be a useful method for delivering a reactive silicon surface to a specific environment. The outer surface of the aggregate may be designed so that the aggregate is stable under certain conditions but separates more easily under other conditions (e.g., changes in pH or solvent polarity). This allows the reactive silicon surface to be selectively delivered to a desired location by controlling and manipulating the conditions affecting the stability of the aggregate. An example of aggregated silicon nanoparticles is shown in the TEM image of Fig. 21.
[0249] In addition, it is worth noting that aggregates can form from the reaction of the silicon core after surface decoration. For example, oxidation of the silicon core over time can lead to cracking of the core. Similarly, when used in electrochemical cells, expansion and subsequent shrinkage due to the alloying / dealloying of lithium can lead to cracking of the core. In such situations, surface decoration, particularly the polymer brush layer, can continue to contribute to the stabilization of the core despite crack formation.
[0250] Accordingly, in some cases, the Si-core may be an aggregate of particles, said aggregate having an outermost surface and a plurality of inner surfaces, and comprising an outer composite particle and an optional inner particle, wherein the optional inner particle comprises a silicon core, and the outer composite particle comprises a silicon core and an outer surface region, said outer surface region is decorated with at least first and second moiety covalently bonded to the silicon core through first and second anchoring components, said outer surface region comprising a first anchoring component covalently bonded to the silicon core and a polymerization initiator, and the second moiety comprising a second anchoring component covalently bonded to the silicon core and one or more functional groups, said outer surface region of the outer composite particle forms the outermost surface of the aggregate, and none of the surfaces of the optional inner particle form part of the outermost surface of the aggregate.
[0251] In some cases, the present disclosure relates to a brush polymer aggregate of particles, said aggregate having an outermost surface and a plurality of inner surfaces, and comprising an outer composite particle and optionally an inner particle, wherein the optionally an inner particle comprises a silicon core, and the outer composite particle comprises a silicon core and an outer surface region, said outer surface region is decorated with first and second moiety covalently bonded to the silicon core through first and second anchoring components, saidly the first moiety comprises a first anchoring component covalently bonded to the silicon core and a polymer moiety, and the second moiety comprises a second anchoring component covalently bonded to the silicon core and one or more functional groups, saidly the outer surface region of the outer composite particle forms the outermost surface of the aggregate, and none of the surfaces of the optionally an inner particle form part of the outermost surface of the aggregate.
[0252] The outer composite particle may include an inner surface region, that is, a surface of a particle that does not form part of the outermost surface of the aggregate. The inner surface region of the outer composite particle may be in contact with the inner surface region of a nearby outer composite particle and / or the surface of an inner particle.
[0253] The internal surface region of the outer composite particle and / or the surface of the inner particle may or may not be functionalized. Whether these surfaces are functionalized will depend on the conditions used to anchor the first and second moieties as well as the conditions used to form the polymer brush.
[0254] For example, when aggregates are present when the first and second moieties are covalently bonded to a silicon surface, the inner surface of the aggregate may not be exposed to the first and second moieties. In this case, the inner surface of the aggregate (i.e., the inner surface region of the outer composite particle and / or the surface of the inner particle) may not be functionalized, i.e., at least 80%, for example at least 90%, for example at least 95% of the surface comprises silicon oxide and / or silicon hydride.
[0255] Other configurations may also be possible. For example, the particles may be completely dispersed when reacting with the first and second moieties. Subsequently, the particles may be in the form of aggregates when forming a polymer brush. This can be easily achieved by removing the dispersion medium, partially redispersing the composite particles so that at least some of them become aggregates of the composite particles, and exposing the aggregates of the composite particles to a polymerization reaction composition to form a brush polymer on the outer surface of the aggregates.
[0256] A polymer brush aggregate of particles is obtained by this method, wherein the inner surface of the aggregate comprises a first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to a silicon core of an inner particle or an outer composite particle, and a second moiety comprising a second anchoring component and one or more functional groups covalently bonded to a silicon core of an inner particle or an outer composite particle.
[0257] The various options described in this specification enable a high level of control over the surface functionalization of silicon particles.
[0258] measurement method
[0259] The properties of surface-grafted polymer brushes can be analyzed through means such as infrared spectroscopy or Raman spectroscopy for functional group identification. Dynamic light scattering can be applied to determine the diameter of the brush polymer composite particles. Thermogravimetric analysis can be used to determine the total mass of the surface-grafted polymer material and, together with gel permeation chromatography analysis of the cut polymer brush chains, can quantify the number of grafted polymer chains per surface area.
[0260] Electrochemical cell applications
[0261] The development of silicon (Si) active anode materials for lithium-ion cells (LICs) holds the potential for greater capacity than current state-of-the-art technologies, such as graphite anodes, but is constrained by fundamental problems such as extreme volume expansion during charge / discharge cycles. Extreme volume expansion typically results in a loss of contact between the solid electrolyte interface (SEI) and the Si surface as the material expands and contracts, leading to repeated exposure of the native Si surface and the formation and loss of the SEI layer. This, in turn, causes rapid depletion of the electrolyte and charge carriers, which can ultimately lead to a premature loss of capacity and battery function. Grafted polymer chains can be introduced to the surface of silicon active materials to mitigate these problems.
[0262] While not bound by theory, it is believed that covalently bonding polymer species to the surface of the active anode material allows the polymer brush to remain attached to the surface through each cycle of charge / discharge-induced volume expansion and contraction. To ensure efficient ion conductivity, the polymer brush is produced within a density range that allows space for ion penetration. To ensure greater stability of the Si particles, the particles themselves can be over-decorated. Over-decoration of the Si particles is defined as sufficient surface protection to prevent the surface from reacting with the electrolyte, thereby inhibiting the formation of an undesirable and destructive SEI layer. In practice, functional groups of the second moiety bonded to the silicon particles act as a pre-formed SEI layer, protecting the underlying silicon from reacting with the electrolyte and consuming excess electrolyte during charge / discharge. In particular, this approach allows for the presence of 'orthogonal' properties on the surface, such as very low surface energy at the moiety bonded to the Si core and a polymer brush layer capable of strongly interacting with the matrix binder polymer. By designing the chemical properties of the moiety in combination with the chemical properties of the polymer brush, the Si-polymer brush interface can be designed to maintain ion conductivity while, for example, stabilizing the Si surface.
[0263] In some cases, the polymer brush may be hydrophilic, while the second moiety (i.e., the functional group of the second moiety) in the base layer may be hydrophobic. In some cases, the polymer brush may be hydrophobic, while the non-initiating moiety (i.e., the functional group of the second moiety) in the base layer may be hydrophobic. In some cases, the polymer brush may be hydrophilic, while the non-initiating moiety (i.e., the functional group of the second moiety) in the base layer may be hydrophilic.
[0264] Si particles comprising a second moiety and a first moiety to which a polymer brush is grafted can be useful as an anode active material.
[0265] To manufacture the negative electrode of a battery, a slurry containing all necessary components may be formed. Generally, this means that one or more anode active materials, one or more binders, a solvent, and optionally a conductive additive may be mixed. By fine-tuning the polymer brush, for example by adjusting its length and polarity, the polymer brush can improve adhesion to the extent that the addition of a binder becomes unnecessary.
[0266] In some cases, the anode may substantially not contain a binder. For example, a substantially binder-free anode may contain, based on the total weight of the anode active material, conductive additive, and binder, about 3 wt% or less of binder, e.g., about 2 wt% or less of binder, e.g., about 1 wt% or less of binder, e.g., about 0.5 wt% or less of binder, e.g., about 0.3 wt% or less of binder, e.g., about 0.1 wt% or less of binder, e.g., about 0.05 wt% or less of binder, and / or may contain such a binder.
[0267] In some cases, the anode may not contain any binder.
[0268] In some cases, silicon particles decorated with polymer brushes can form a network connected by the polymer brushes, and the polymer brush connections provide elasticity to the connected network across the anode, thereby protecting the structural integrity of the anode as well as the structural integrity of the individual silicon particles during battery cycling. The nature of the connections between the polymer brushes may include one or more of covalent bonds, ionic bonds, van der Waals interactions, etc.
[0269] In some cases, silicon particles decorated with polymer brushes can form a network connected by polymer brushes and polymer binders, and the connection between the polymer brushes and polymer binders provides elasticity to the connected network throughout the anode, thereby protecting the structural integrity of the anode as well as the structural integrity of the individual silicon particles during battery cycling. The nature of the connection between the polymer brushes and the polymer binders may include one or more of covalent bonds, ionic bonds, van der Waals interactions, etc.
[0270] Similarly, similar improvements can be made to anode materials such as graphite particles, carbon-coated silicon particles, and Si / C composite particles. In current standard energy storage devices, the anode composition contains a component that enhances electrical conductivity, e.g., carbon black, and a binder component, e.g., PVDF, which serves to maintain the overall anode structure, keep particles close together, and maintain electrical conduction pathways for the particles through the carbon black network. In the standard composition, the binder, e.g., PVDF, is merely a free-standing additive. On the other hand, polymer brushes are covalently bonded to the particles and entangled with nearby particles, providing self-healing properties through cycling-induced volume expansion and contraction phenomena, thereby providing an overall structure that is more robust and chemically bonded than the standard PVDF-type binder. Incorporating organic functional groups for electrical conductivity into PB, such as those possessing overlapping p-bonds (sp and sp2), will further enhance the characteristics of the anode function. Considering such graphite structures, more robust composite anode structures of various Si-graphite compositions can be generated. A composite anode structure can be expressed as follows:
[0271] (Si-OC-PB)x (Si-C-PB)y (Graphite-PB)z + electrical conductivity enhancer
[0272] As described above, conventional binders such as PVDF can be completely replaced with PB.
[0273] The slurry may comprise one or more anode active materials, a solvent, optionally a binder, and optionally a conductive additive. The addition of a solvent enables easy fabrication of the electrode. The slurry composition may be formulated to a suitable viscosity so that it can be processed into a cathode, for example, by slot-die coating. When measured at 25°C, the slurry composition may generally have a dynamic viscosity of about 2 to about 50 Pa·s, for example, about 5 to about 40 Pa·s, or about 5 to about 25 Pa·s. The slurry composition may generally contain about 50 to 90 wt% solids, for example, about 60 to 80 wt% solids, or about 68 to 73 wt% solids, with the remainder being a dispersion medium. The method of forming the slurry composition may not be important, and once formed, it may generally be stable at room temperature for at least one day or at least one week. In this context, "stable" means that solid particles do not settle. Although the slurry composition may be formed by combining the components in any order, the best results can be obtained by following a method comprising the steps of providing a composition comprising the composite particles of the present disclosure, a binder, optionally a conductive additive, and optionally a dispersion medium, adding the dispersion medium to the composition, and mixing to provide a slurry composition having a suitable viscosity.
[0274] The present disclosure also relates to an electrochemical cell comprising the anode of the present disclosure, e.g., a secondary lithium-ion cell. Such a cell may comprise a cathode, a separator disposed between the anode and the cathode, said cathode, anode, and separator form an electrode assembly, and the cell further comprises a housing for the electrode assembly. Refer to FIG. 22 for a schematic diagram of a battery. A non-aqueous electrolyte enables lithium-ion transport between the composite cathode and the anode. The housing is generally sealed so that the electrolyte is retained within the housing. The housing may include terminals that are electrically in contact with the anode and the composite cathode.
[0275] These cells can be combined to form a battery system (i.e., an array of cells).
[0276] The present disclosure also relates to an electric device comprising a cell of the present disclosure. For example, the present disclosure relates to a vehicle comprising a cell (or battery system) of the present disclosure. The vehicle may be an electric vehicle, such as an automobile, truck, bus, scooter, motorcycle, bicycle, or similar.
[0277] Furthermore, the present disclosure relates broadly to electrochemical cells, and more specifically to polymer brushes designed for electrodes within such cells. In particular, polymer brush structures and arrangements are introduced that aim to improve uniform lithium deposition and promote strong adhesive bonding between an electroactive layer and an electrically conductive support. In some embodiments, the polymer brush layer described herein comprises first and second moietyes that can be co-immobilized.
[0278] It has been found that working atoms within the polymer, including -N, -O, -S, and -F, exhibit the ability to interact with Li, and accordingly, local Li + Reduces concentration and Li +It promotes the uniform rearrangement of the distribution. This leads to a reduction in nucleation overpotential and enables planar Li deposition. Notably, He et al. stabilized Li deposition using polydopamine (pDA), where the hydroxyl groups of pDA serve as favorable nucleation sites for subsequent Li deposition (Energy Stor. Mater. 2019, 23, 418-426). In addition, -NH2, etc. N - The contained functional groups serve as lithium-affinity sites. The abundant functional groups in pDA effectively mitigate uncontrolled dendritic growth during repetitive Li plating and stripping cycles. On the other hand, Liu et al. synthesized an organic supramolecular protective layer (OSPL) on Cu foam via the condensation polymerization of melamine and cyanuric acid (Energy Stor. Mater. 2020, 32, 261-271). Amino, carbonyl, and triazine groups uniformly distributed within the OSPL [affect] concentrated Li + It enables the rearrangement of the flux. In addition, Li et al. use dopamine for normalized lithium growth for lithium metal anodes, and the poly( N -isopropylacrylamide) brushes were utilized (Agew. Chem. 2019, 131, 18414-18419). Additionally, the presence of abundant polar groups enables the formation of hydrogen bonds, imparting elasticity and accommodating volume expansion during Li plating. Furthermore, various other polymers have been utilized to improve current collector (CC) and overall cell performance. To address the inherent low conductivity of polymers, various strategies are being explored, including the incorporation of conductive agents or the use of conductive polymers such as poly(3,4-ethylenedioxythiophene) (PEDOT) (Electrochem. Commun. 2019, 102, 1-4 and Angew. Chem. Int. Ed. 2011, 50, 6884-6887).
[0279] A typical battery includes essential components such as an anode, cathode, separator, electrolyte, outer casing, and sealing components. The current collector (CC) performs a critical function within the battery system. First, the current collector supports the electroactive layer (anode or cathode) by acting as a substrate for casting a slurry, which is a mixture containing active material, a polymer binder, and conductive additives. Second, the CC enables the flow of electrons between the electrode material and the external circuit. Various advantages can be achieved by manipulating the characteristics of the CC. Furthermore, strengthening the interface between the active material and the CC through a wider contact area creates additional electron pathways, thereby reducing the internal resistance of the cell.
[0280] The present disclosure focuses on improving the performance, stability, and efficiency of current collectors in lithium-ion batteries (LIBs) and lithium metal batteries (LMBs) by introducing polymer brushes (PBs) to enhance properties. By integrating PBs into CCs, the goal is to meet the evolving demands of next-generation LIB applications across various industries. The present disclosure relates to a scalable technique for fabricating polymer brushes on current collectors tailored for electrochemical cells, including alkali metal-based or anode-free systems. This technique enables the creation of multifunctional current collectors with various polymer brush configurations. Furthermore, the present disclosure introduces a method for fabricating multifunctional current collectors that utilize the enhanced lithium affinity imparted by polymer brushes to promote uniform lithium deposition in some embodiments and optimize performance in alkali metal-based or anode-free configurations.
[0281] electrically conductive support
[0282] Generally, copper (Cu) and aluminum (Al) are anodes (0-1.5 V vs. Li / Li) respectively. + ) and cathode (3-4.7 V vs. Li / Li +It is most commonly applied as an electrically conductive support for the ) layer. This preference is based on electrochemical stability within each potential range. Specifically, Al is 0.26 V (vs. Li / Li + Cu cannot be utilized as an anode electrically conductive support due to its tendency to undergo alloying reactions with Li. On the other hand, Cu is within the operating voltage range of the cathode active material, at 3.5 V (vs. Li / Li). + It is easily soluble above ) However, various electrically conductive supports are available, including but not limited to other metal foils (e.g., nickel and stainless steel), metallized polymer films (e.g., aluminumized polyester films), electrically conductive polymer films, polymer films coated with electrically conductive materials, electrically conductive polymer films coated with conductive metals, and polymer films containing dispersed conductive particles. Other possible electrically conductive supports include expanded metal, metal mesh, metal grid, expanded metal grid, metal wool, woven carbon fabric, woven carbon mesh, non-woven carbon mesh, and carbon felt.
[0283] In the method of the present disclosure, a polymer brush is formed on the surface of an electrically conductive support. A first moiety having a polymerization initiator is immobilized thereon on the surface. The first moiety acts as an initiator for a polymerization reaction.
[0284] After the formation of the polymer brush, the resulting electrically conductive support is removed from the polymerization medium.
[0285] Brush polymers can be formed from one or more monomers. That is, polymer brushes may contain one or more repeating units. For example, a polymer brush may be a block copolymer containing two different repeating units. To form a block copolymer, an electrically conductive support is first reacted with one type of monomer, and then the electrically conductive support is reacted with another type of monomer. Random block copolymers can be formed by reacting an electrically conductive support with two or more different monomers simultaneously.
[0286] The present disclosure relates to a scalable technique for fabricating polymer brushes on current collectors customized for electrochemical cells comprising alkali metal-based or anode-free systems. This technique enables the creation of multifunctional current collectors having various polymer brush configurations. Furthermore, the present disclosure introduces a method for fabricating multifunctional current collectors that utilize the enhanced lithium affinity imparted by the polymer brushes to promote uniform lithium deposition in some embodiments and optimize performance in alkali metal-based or anode-free configurations.
[0287] Exemplary Embodiment 1 - Immobilization of (p-chloromethyl)phenyltrimethoxysilane (CPTMS) and 4-aminopropyltrimethoxysilane (APTMS)
[0288] This example illustrates a procedure for covalently bonding CPTMS (first moiety precursor) and APTMS (second moiety precursor) to an electrically conductive support, as illustrated in process (506) of FIG. 32.
[0289] The surface modification process will begin with the use of clean Cu foil, upon which CPTMS and APTMS polymerization initiators will be applied using a chemical vapor deposition method. The substrates will be arranged on a rack and introduced into a vacuum oven containing eight vials of 100 μL CPTMS (Gelest) and eight vials of 100 μL APTMS (Sigma-Aldrich) for 150 minutes at approximately 45°C. The pressure gauge will be adjusted to reach -1.0 bar to allow the CPTMS and APTMS to evaporate and be chemically deposited onto the electrically conductive support. Subsequently, the electrically conductive support will be removed from the oven and subjected to an annealing process at approximately 100°C for 1 hour.
[0290] Exemplary Embodiment 2: Wet Chemical Deposition of CPTMS on Cu
[0291] An alternative wet chemical approach for surface immobilizing a polymerization initiator on an electrically conductive support is disclosed and comprises the following steps. First, a solution composed of 1% acetic acid and 1% CPTMS will be thoroughly mixed in ethanol. Subsequently, the electrically conductive support will be immersed in the resulting solution for 15 minutes to immobilize the polymerization initiator on the Cu surface. Next, the modified electrically conductive support will be thoroughly washed with acetone to remove excess reagent, followed by annealing at 100°C for 3 minutes. After annealing, a comprehensive cleaning process using acetone will be performed to remove residual contaminants. Finally, the sample will be left to air dry. Verification of surface modification is Kr This can be performed by measuring the water contact angle using a mobile surface analyzer. In addition, the presence of CPTMS on the surface can be verified using Fourier transform infrared spectroscopy (FT-IR).
[0292] Exemplary Embodiment 3: Chemical Vapor Deposition of APTMS and Derivatization Using BiBB
[0293] A clean Cu foil sample will be placed in a glass container along with two sample vials, each containing 100 μL of APTMS. The container will be sealed with a lid and placed in an oven set to 30°C for 1 hour. Subsequently, the resulting sample will be annealed at 100°C for 1 hour. The APTMS-grafted Cu foil will then be added to a solution containing dichloromethane, triethylamine, and BiBB. The sample will be stirred on a shaking table at 80 rpm for 1 hour. After washing with acetone, the resulting sample will be sonicated sequentially in dichloromethane and acetone for 5 minutes each.
[0294] Exemplary Embodiment 4: Chemical Vapor Deposition of 3-Trimethoxysilylpropyl 2-Bromo-2-Methyl-Propionate (BPTMS)
[0295] Similar to Exemplary Embodiment 1, a clean Cu foil will be placed in a sealed container along with a small vial containing 50 μL of BPTMS and 50 μL of APTMS. This sealed container containing both the Cu foil and BPTMS will then be placed in an oven set to 45°C for 2.5 hours. Afterward, the sample will be annealed in an oven at 100°C for 1 hour.
[0296] Exemplary Embodiment 5: Preparation of a reaction composition for forming a polymer brush
[0297] This example illustrates the preparation of a reaction composition (process (505) of FIG. 5) for the method disclosed herein.
[0298] As illustrated in process (502) of FIG. 5, 76 μL of tris[2-(dimethylamino)ethyl]amine (Me6TREN, a commercially available ligand in grades >98% from Alfa Aesar), 15.9 mL of water, and 16 mL of a catalyst solution containing 324 mg / L of Cu(II) supplied from solid Cu will be added to a glass container. Subsequently, an additional 484 mL of water, 410 mL of ethanol (grade 96% from Sigma-Aldrich), and 75 mL of acrylamide monomer (Sigma-Aldrich) will be added and mixed. In a separate container, process (503) of FIG. 5 will involve dissolving 4,000 mg of sodium ascorbate (catalytic activator from Sigma-Aldrich) in 15 mL of water. Immediately after dissolution, this solution will be combined with the first solution. After 5 minutes, the resulting reaction composition solution will be applied to form a polymer brush.
[0299] Exemplary Embodiment 6: Manufacture of an electrically conductive support decorated with a poly(acrylamide) brush
[0300] The CPTMS and APTMS co-immobilized Cu foil of Exemplary Example 1 will be used as a substrate for growing a poly(acrylamide) brush. In a conical flask, 15 mL of acrylonitrile and 50 mL of DMSO will be combined and purged with N2. Separately, 2 mg of anhydrous CuCl2 and 3.2 mg of tris(2-pyridyl-methyl)amine (TPMA) will be dissolved in DMF and purged with N2. Then, 0.75 mL of this solution will be added to the acrylonitrile / DMSO mixture. Additionally, 0.9 mL of tin(II) 2-ethylhexanoate (Sn(EH)2) dissolved in 50 mL of DMSO will be prepared, and 1 mL of this mixture will be added to the acrylonitrile / DMSO solution to form a reaction composition for growing the poly(acrylamide) brush. The BPTMS-anchored Cu foil will be immersed overnight in this reaction composition to enable the growth of poly(acrylamide) brushes on the Cu foil. The thickness and uniformity of the poly(acrylamide) brush layer can be measured using ellipsometer measurements.
[0301] Exemplary Embodiment 7: Manufacture of an electrically conductive support decorated with a poly(acrylamide) brush
[0302] Various batches of CPTMS precursors will be tested, and subsequently, polymerization of acrylamide to form a poly(acrylamide) brush will be performed. The polymerization initiator-anchored electrically conductive support prepared in Exemplary Example 2 will be used to grow poly(acrylamide) on the surface of the electrically conductive support. The reaction composition solution of Exemplary Example 5 will be transferred to a three-necked round-bottom flask and degassed with an inert gas for 10 minutes. Afterward, the initiator-decorated electrically conductive support will be left in the solution for 2 hours to grow the poly(acrylamide) brush. The resulting sample will be cleaned by sonication in water and acetone for 5 minutes each.
[0303] Exemplary Embodiment 8: Manufacture of an electrically conductive support decorated with a poly(acrylonitrile) brush
[0304] The BPTMS and APTMS co-immobilized foil of Exemplary Example 4 will be used as a substrate for growing poly(acrylonitrile) (PAN) brushes. In a conical flask, 15 mL of acrylonitrile and 50 mL of DMSO will be combined and purged with N2. Separately, 2 mg of anhydrous CuCl2 and 3.2 mg of tris(2-pyridyl-methyl)amine (TPMA) will be dissolved in DMF and purged with N2. Then, 0.75 mL of this solution will be added to the acrylonitrile / DMSO mixture. Additionally, 0.9 mL of tin(II) 2-ethylhexanoate (Sn(EH)2) dissolved in 50 mL of DMSO will be prepared, and 1 mL of this mixture will be added to the acrylonitrile / DMSO solution to form a reaction composition for growing PAN brushes. BPTMS and APTMS co-immobilized Cu foil will be immersed overnight in this reaction composition to enable the growth of PAN brushes on the Cu foil. The thickness and uniformity of the polymer brush layer can be measured using ellipsometer measurements.
[0305] Exemplary Embodiment 9: Manufacture of an electrically conductive support decorated with a fluorinated polymer brush
[0306] A mixture comprising 0.6 mL of a mixture containing 25 mL of water, 25 mL of isopropanol, 0.6 mL of PMDETA, 7.6 mL of 1H,1H,2H,2H-heptadecafluorodecyl methacrylate (HFDMA), and 0.4 mL of ethylene glycol dimethacrylate (EDGMA) will be prepared in a round-bottom flask. After mixing, the reaction mixture is expected to form two phase-separated layers, and the upper layer will be selected for further use. The initiator-anchored electrically conductive support of Exemplary Example 3 will be applied to carry out the reaction with the polymerization solution for 1 hour. Successful coating by a fluorinated polymer brush can be indicated using the water contact angle of the resulting substrate.
[0307] Exemplary Embodiment 10: Assembly and Evaluation of a Coin Cell Using a Cu Electrically Conductive Support Decorated with Fluorinated Polymer Brushes
[0308] The composite NMC cathode will be prepared by compressing NMC111 material, Super P, and polyvinylidene fluoride (PVDF) in a weight ratio of 90:5:5 onto an Al current collector using NMP (N-methyl-2-pyrrolidone) as a solvent. The cathode will be thoroughly dried to remove residual solvent before cell assembly. The active material loading on the aluminum current collector will be about 8 mg / cm2. Cell assembly will be performed in an argon-filled glove box (both oxygen and moisture less than 0.1 ppm) using a copper foil decorated with a 16 mm diameter fluorinated polymer brush of Exemplary Example 9, a 12 mm diameter cathode disk, and a 19 mm diameter Celgard 2400 separator. As the electrolyte, 2 wt% LiNO3 will be added to 1 M LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) in DME / DOL (1,2-dimethoxyethane / 1,3-dioxolane) 1:1 (v / v). Approximately 150 μl of electrolyte will be added to each coin cell. Cells with untreated Cu current collectors will be manufactured according to the same procedure described above. All cells will be tested using a Maccor battery tester. Anode-free cells will undergo formation cycles for 3 cycles at a C / 10 rate (1C = 180 mA / g), followed by cycling with C / 5 charge and C / 3 discharge. The potential range is 3.5 to 4.4 V relative to Li / Li+. The specific capacity and capacity retention rate curves of cells with and without polymer brush decoration will be compared.
[0309] Exemplary Embodiment 11: Assembly and Evaluation of a Coin Cell Using a Cu Electrically Conductive Support Decorated with Poly(Acrylonitrile) Brushes
[0310] The coin cell battery will be assembled using the same procedure described in Exemplary Embodiment 8, except that it utilizes a Cu electrically conductive support decorated with PAN brushes. Cell performance including specific capacity and capacity retention rate curves will be produced.
[0311] Exemplary Embodiment 12: Assembly and Evaluation of a Coin Cell Using a Cu Electrically Conductive Support Decorated with Polyacrylamide Brushes
[0312] The coin cell battery will be assembled using the same procedure described in Exemplary Embodiment 6, except that it utilizes a Cu electrically conductive support decorated with polyacrylamide brushes. Cell performance including specific capacity and capacity retention rate curves will be produced.
[0313] Si / C composite particles
[0314] Exemplary Embodiment 13: Synthesis of Si / C composites from Si micropowder using mechanical milling technology.
[0315] A general method for synthesizing Si / C composites from Si micropowder is described herein, and a process flow diagram for the mechanochemical synthesis of Si / C composites is illustrated in FIG. 26. Micron-sized silicon powder will be mixed with polymer powder. In the dry milling of the Si and polymer powders, 8,500 mg of 325 mesh Si powder and 1,000 mg of polyvinylidene chloride (PVDC) will be ground using an agate mortar and pestle. The powders will be mixed with a yttria-stabilized zirconia (YSZ) medium in a 12:1 mass ratio and sealed in a friction milling or ball milling mortar under an argon atmosphere. The sealed mortar will then be milled at a speed in the range of 500 rpm for 4 hours. The product will be collected, loaded into an alumina crucible, and placed in the center of a quartz tubular furnace with a cross-sectional diameter of 4 inches. The system will then be evacuated to a base pressure of <0.05 T and back-charged with argon to atmospheric pressure. The furnace will be heated to 900°C at a heating rate of 1°C / min and maintained at that temperature for 2 hours in argon gas to produce a Si / C composite. The resulting Si / C composite product will then be coated with a graphite-carbon layer via chemical vapor deposition (CVD). The thermal decomposition of acetylene, a hydrocarbon precursor, will be carried out at 600°C in an inert diluent / carrier gas. This step will result in the formation of Si / C composite particles (Compound 1) with a graphite-carbon layer.
[0316] Exemplary Embodiment 14: Synthesis of Si / C composites from metallurgical grade Si (MG-Si).
[0317] A process flow diagram for the MG-Si-based synthesis of Si / C composites is shown in Fig. 27. The MG-Si chips will be ground into powder using an agate mortar and pestle. The MG-Si powder will be mixed with a YSZ medium at a mass ratio of 12:1 and sealed in a friction milling or ball milling apparatus under an argon atmosphere. The sealed apparatus will then be milled at 1,000 rpm for 6 hours. The milled MG-Si powder may be etched using an iron etchant to remove metallic impurities. 50 mM Fe(NO3)3 will be mixed with 3 M HF in ethanol under constant magnetic stirring. After 2 hours, the precipitated product will be collected via centrifugation and washed with DI-H2O until neutralized. The etched product will subsequently be coated with polyvinylidene chloride (PVDC) via emulsion polymerization in methyl-ethyl ketone and DI-H2O using sodium dodecylbenzenesulfonate as a surfactant. The emulsion will be obtained through probe sonication and magnetic stirring for 6 hours. Afterward, the product will be collected by centrifugation and dried. Once dried, the product will be collected, loaded into an alumina crucible, and placed in the center of a quartz tubular furnace with a cross-sectional diameter of 4 inches. The system will then be evacuated to a base pressure of <0.05 T and back-charged to atmospheric pressure with argon gas. The furnace will then be heated to 900°C at a heating rate of 1°C / min and maintained at that temperature for 2 hours in an argon atmosphere. The resulting Si / C composite material will subsequently be coated with a graphite-carbon layer via CVD as described in Exemplary Embodiment 13 to produce Si / C composite particles (Compound 2) having a graphite-carbon layer.
[0318] Exemplary Embodiment 15: Synthesis of Si / C composites from silica using a magnesium thermal reduction method.
[0319] A general method for synthesizing Si / C composites from silica microparticles is described herein, and a process flow diagram is illustrated in FIG. 28. 3,000 mg of silica microparticle powder and 6,000 mg of magnesium powder will be ground together in an inert environment using an agate mortar and pestle. While still in an inert environment, the ground mixture will be loaded into an alumina crucible and placed in the center of a quartz tubular furnace with a cross-sectional diameter of 4 inches. The system will then be evacuated to a base pressure of <0.05 T and back-charged with argon to atmospheric pressure. The furnace will then be heated to 600°C at atmospheric pressure under a constant flow at a heating rate of 5°C / min. Once the temperature setpoint is reached, the furnace will be maintained at the 600°C setpoint for 30 minutes to allow the system to equilibrate. The reaction will be maintained at this temperature, pressure, and flow rate setpoint for 4 hours. When the reaction is complete, the furnace will be cooled in an inert gas environment under a constant flow before the product material is collected. The collected material will then be treated with 1 M HCl in ethanol under constant stirring for 12 hours. Afterward, the product will be collected by centrifugation and drying. The resulting porous silicon material will then be coated with a graphite-carbon layer via CVD as described in Exemplary Embodiment 13 to produce Si / C composite particles (Compound 3) having a graphite-carbon layer.
[0320] Exemplary Embodiment 16: Synthesis of Si / C composites from silicon nanoparticles.
[0321] A general method for synthesizing Si / C composites from silicon nanoparticles is described herein, and a process flow diagram is illustrated in FIG. 29. 10,000 mg of silicon nanoparticles will be loaded into a graphite crucible and placed in the center of a quartz tubular furnace with a cross-sectional diameter of 4 inches. The system will then be evacuated to a base pressure of <0.05 T and back-charged to atmospheric pressure with an inert gas such as N2 or Ar. The furnace will then be heated to 600°C at atmospheric pressure in an inert gas environment under a constant flow rate of 5°C / min. Once the temperature setpoint is reached, the furnace will be maintained at the 600°C setpoint for 30 minutes to allow the system to equilibrate. Then, a hydrocarbon precursor will be introduced at atmospheric pressure at a flow rate of 10% of the total flow rate containing an inert diluent. The reaction will be maintained at this temperature, pressure, and flow rate setpoint for 8 hours. Once the reaction is complete, the product material can be cooled in an inert gas environment under a constant flow before being collected as compound 4.
[0322] Exemplary Embodiment 17: Immobilization of 4-(chloromethyl)benzenediazonium tetrafluoroborate on Compound 1
[0323] The Si / C composite material will be decorated using 4-(chloromethyl)benzenediazonium tetrafluoroborate (CBD) as the first moiety precursor.
[0324] First, CBD will be synthesized by adding 5 g of 4-aminobenzyl alcohol to 50 mL of 37% HCl and reacting in a dark place for 24 hours. Subsequently, 35 mL of 48% tetrafluoroboric acid will be added to the reaction mixture at 0°C and stirred for 15 minutes. 15 mL of 20 wt.% sodium nitrite solution will be slowly added to the reaction mixture and left to react for 20 minutes. The reaction mixture will then be placed in a freezer overnight, washed with cold DI water, methanol, and diethyl ether, dried under vacuum for 1 hour, and stored in a freezer until use. CBD can be used in a chemically reducing environment for attachment to the graphite surface.
[0325] The reaction to immobilize CBD as an ATRP initiator on the graphite-carbon coating surface of a Si / C composite material will be carried out using Compound 1. 17.2 g of Compound 1 will be dispersed in DI water by sonication and stirring, and then 2.5 g of CBD will be added. Sodium ascorbate will be slowly added over 3 hours, and the reaction mixture will be stirred for an additional 5 hours. The final product (Compound 5) will then be washed with DI water by centrifugation or filtration.
[0326] Exemplary Example 18: Co-immobilization of 4-(chloromethyl)benzenediazonium tetrafluoroborate and 4-carboxybenzenediazonium tetrafluoroborate on Compound 1
[0327] The Si / C composite material will be decorated using 4-(chloromethyl)benzenediazonium tetrafluoroborate (CBD) and 4-carboxybenzenediazonium tetrafluoroborate as first and second moiety precursors.
[0328] First, CBD will be prepared as described in Exemplary Example 17. For the second moiety precursor, 0.5 g of 4-aminobenzoic acid will be used instead, and the same procedure for CBD synthesis will be followed. The reaction to immobilize both the first and second moietys on the graphite-carbon coating surface of the Si / C composite material will be carried out using Compound 2. 7.5 g of Compound 1 will be dispersed in DI water by sonication and stirring, and then 1.0 g of CBD and 0.1 g of 4-carboxybenzenediazonium tetrafluoroborate will be added. Sodium ascorbate will be slowly added over 3 hours, and the reaction mixture will be stirred for an additional 5 hours. The final product (Compound 6) will then be washed with DI water by centrifugation or filtration.
[0329] Exemplary Embodiment 19: Immobilization of 4-(chloromethyl)benzenediazonium tetrafluoroborate on Compound 2
[0330] CBD will be immobilized on the graphite-carbon coating surface of Compound 2 using the same procedure described in Exemplary Example 17. The final product (Compound 7) will be collected and used in the next polymerization step.
[0331] Exemplary Embodiment 20: Immobilization of 4-(chloromethyl)benzenediazonium tetrafluoroborate on Compound 3
[0332] CBD will be immobilized on the graphite-carbon coating surface of Compound 3 using the same procedure described in Exemplary Example 17. The final product (Compound 8) will be collected and used in the next polymerization step.
[0333] Exemplary Embodiment 21: Immobilization of 4-(chloromethyl)benzenediazonium tetrafluoroborate on Compound 4
[0334] CBD will be immobilized on the graphite-carbon coating surface of Compound 4 using the same procedure described in Exemplary Example 17. The final product (Compound 9) will be collected and used in the next polymerization step.
[0335] Exemplary Embodiment 22: Formation of a polyacrylic acid polymer brush on Compound 5
[0336] Polymer brushes will be grown from attached initiator sites by dispersing a CBD-decorated Si / C composite material (Compound 5) in a mixture of DI water and isopropanol. The dispersion will first be stirred for 10 minutes and then sonicated for 10 minutes. A tertiary-butyl acrylate monomer solution will be prepared in the presence of an ATRP catalyst and then added to the dispersion containing the Si / C composite material. Sodium ascorbate dissolved in water will then be added to the reaction mixture containing the dispersed Si / C composite material to initiate polymerization, and this reaction will be carried out for 2 hours. The Si / C composite material containing the attached poly(tertiary-butyl acrylate) brushes will be purified by washing with dichloromethane and centrifugation. The attachment of polymer brushes to the surface of the Si / C composite material can be confirmed by XPS. (The composite material is irradiated with X-rays, causing the emission of electrons whose energy is analyzed to determine the elemental composition and chemical bonds.) XPS should clearly show the ester bonds of the acrylates present as well as the graphite coating. To prepare a polyacrylic acid brush, a Si / C composite material containing a PtBA polymer brush will be dispersed in dichloromethane, 0.5 wt.% of methanesulfonic acid relative to the weight of the Si / C composite material will be added, and the mixture will be left to react for 2 hours. The material will be washed twice with dichloromethane by centrifugation to prepare a polyacrylic acid polymer brush (Compound 10) on the surface of the Si / C composite material, which can be confirmed by FT-IR.
[0337] Exemplary Embodiment 23: Formation of a polyacrylic acid polymer brush on Compound 6
[0338] A polyacrylic acid polymer brush will be grafted onto Compound 6 using the same procedure described in Exemplary Example 22. The final product will be collected as Compound 11 as depicted in FIG. 25.
[0339] Exemplary Embodiment 24: Formation of a polyacrylic acid polymer brush on Compound 7
[0340] A polyacrylic acid polymer brush will be grafted onto Compound 7 using the same procedure described in Exemplary Example 22. The final product will be collected as Compound 11 as depicted in FIG. 25.
[0341] Exemplary Embodiment 25: Formation of a polyacrylic acid polymer brush on Compound 8
[0342] A polyacrylic acid polymer brush will be grafted onto Compound 8 using the same procedure described in Exemplary Example 21. The final product will be collected as Compound 13.
[0343] Exemplary Embodiment 26: Formation of PPFS polymer brush on Compound 5
[0344] Examples of Si / C composite materials containing poly(pentafluorostyrene) (PPFS) polymer brushes are described herein. For the synthesis of polyacrylic acid polymer brushes, using the same technique as described in Exemplary Embodiment 17, a Si / C composite material containing an ATRP initiator on its surface will be dispersed in DI water and isopropanol. A pentafluorostyrene monomer solution will be prepared in the presence of an ATRP catalyst and then added to the dispersion containing the Si / C composite material. Sodium ascorbate dissolved in water will then be added to the reaction mixture containing the dispersed Si / C composite material to initiate polymerization, and this reaction will be carried out for 2 hours. The material will be washed twice with dichloromethane by centrifugation to produce PPFS polymer brushes (Compound 14) on the surface of the Si / C composite material, which can be confirmed by FT-IR.
[0345] Exemplary Embodiment 27: Manufacturing of battery electrode and coin cell assembly using Si / C composite material decorated with polymer brushes (Compound 10)
[0346] A slurry will be prepared to manufacture an anode electrode sheet by utilizing a Si / C composite material combined with a polymer brush, as described in detail in Exemplary Example 22. The composition will consist of a Si / C composite material coated with a polymer brush (compound 5, 0.5 g), conductive carbon (Kappa 10, 15 mg), a 1% CNT dispersion in water (Tuball, 0.5 g), a 5% polyacrylic acid solution in H2O (0.5 g), and additional H2O (2.1 g). This slurry will be thoroughly mixed using a planetary mixer. Subsequent Hegman gauge characterization may be used to confirm that there are no aggregated particle sizes exceeding 20 μm. The resulting slurry will be used to coat the electrode sheet with a doctor blade set at 150 μm intervals. The coated foil will then be dried in a vacuum oven set at 50°C for at least 12 hours. A coin cell will be assembled in a glove box for performance evaluation of the resulting electrode. Lithium metal will be used as the counter electrode, and 5% FEC in a 1 M lithium hexafluorophosphate solution in EC / EMC will be used as the electrolyte. The specific capacity and capacity retention rate curves can be compared with electrodes fabricated without polymer brush decoration.
[0347] Exemplary Embodiment 28: Manufacturing of battery electrode and coin cell assembly using Si / C composite material (Compound 14)
[0348] The coin cell battery will be assembled using the same procedure described in Exemplary Embodiment 26, except that it utilizes a Si / C composite material (Compound 14) having poly(pentafluorostyrene) brush decoration. Cell performance, including specific capacity and capacity retention rate curves, will be measured.
[0349] Exemplary Embodiment 29: Manufacturing of battery electrode and coin cell assembly using Si / C composite material (Compound 13)
[0350] The coin cell battery will be assembled using the same procedure described in Exemplary Embodiment 27, except that it utilizes a Si / C composite material (Compound 13) having a polyacrylic acid brush decoration. Cell performance, including specific capacity and capacity retention rate curves, will be measured.
[0351] Exemplary Embodiment 30: Manufacturing of battery electrode and coin cell assembly using Si / C composite material (Compound 1)
[0352] The coin cell battery will be assembled using the same procedure described in Exemplary Embodiment 27, except that it utilizes a Si / C composite material (Compound 1) without polymer brush decoration. Cell performance, including specific capacity and capacity retention rate curves, will be measured. The inventors anticipate superior performance from a cell having a Si / C composite material decorated with polymer brushes.
[0353] The disclosure of this specification is further illustrated by the following non-limiting examples.
[0354] Examples
[0355] The present disclosure is further illustrated by the following non-limiting examples. The following reagents and abbreviations are used in the examples:
[0356] Methanol (MeOH, 99.85%, HPLC-grade, Chemsolute), Ethanol (EtOH, 96%), Toluene (99.8%, HPLC-grade, Chemsolute), Dichloromethane (DCM, 99.9%, HPLC-grade, Chemsolute), Hydrofluoric Acid (HF, 48% in water, Sigma-Aldrich), Silicon Nanomaterials (SkySpring Nanomaterials, D 50 = 100 nm), silicon nanomaterials (MTI, D 50= 100 nm), tertiary-butyl acrylate (tBA, 98%, Sigma-Aldrich), 4-vinylbenzyl chloride (4-VBC, 90%, Sigma-Aldrich), pentafluorostyrene (PFS, >98%, Tokyo Chemical Industry), allylamine (98%, Aldrich), acrylonitrile (≥99%, Aldrich), acetone (>99%), 4-decylbenzenediazonium tetrafluoroborate (in-house synthesized), tertiary-butyl methacrylate (tBMA, >98%, Tokyo Chemical Industry), isopropanol (iPrOH, 99.8%, HPLC grade, Chemsolute), sodium L-ascorbate (NaAsc, ≥98%, Sigma-Aldrich), DI water (Silhorko, M22-F water softening plant, RO B1-2 reverse osmosis plant and Silex 2BS Produced using a mixed-bed plant, ensuring conductivity of less than 0.5 μS, indicating low ion content, i.e., less than about 0.1 mg / l), methanesulfonic acid (≥99%, Sigma-Aldrich), potassium bromide (KBr, spectroscopic grade, Roth), aluminum oxide (Al2O3, Supelco), graphite (SLC1520T, Superior, Superior Graphite), lithium hydroxide (LiOH), sulfuric acid (1%).
[0357] "Ultrasonic processor" refers to the Bandelin Sonorex Super RK100 ultrasonic processor (35 kHz ultrasonic frequency, 80 W nominal ultrasonic output).
[0358] "Centrifuge" refers to Centrifuge 5810 (Eppendorf).
[0359] XPS measurements were performed using a Kratos Axis Ultra-DLD spectrometer with a monochromatic Al K-alpha X-ray source. The survey spectrum was obtained by averaging two measurements from 0 to 1400 eV at a pass energy of 160 eV. Data processing was performed using CasaXPS v2.3.15 software.
[0360] The ATR IR spectrum was recorded using a Spectrum Two FT-IR spectrometer (PerkinElmer).
[0361] "Shaking plate" refers to the orbital shaking plate PSU-10i (Grant Instruments Ltd).
[0362] The water contact angle (WCA) is Kr Measurements were taken using a Mobile Surface Analyzer. At five separate points, the contact angles of DI-water and CH2I2 droplets were measured. Using the software ADVANCED v. 1.14, the surface free energy (SFE) can be calculated. SFE represents the maximum surface tension of a liquid wetting a solid surface under ideal conditions. Therefore, materials with a high SFE are easier to wet than materials with a low SFE, and materials with a low SFE will generally exhibit a higher water contact angle than materials with a higher SFE.
[0363] Example 1: Co-immobilization of 4-vinylbenzyl chloride and tertiary-butyl acrylate
[0364] Si particles were decorated using 4-vinylbenzyl chloride (4-VBC) and tertiary-butyl acrylate (tBA) as first and second moiety precursors.
[0365] First, Si particles were treated with HF to form H-terminated Si surfaces: In a polypropylene conical flask equipped with a magnetic stirring bar, 20 g of silicon nanomaterials (SkySpring Nanomaterials, D50 = 100 nm) were suspended in 920 mL of methanol by stirring for 10 minutes and sonicating in a bath sonicator for 10 minutes. The suspension was returned to the stirring plate, and 80 mL of hydrofluoric acid was added to the flask. The contents of the flask were then stirred for 10 minutes (500 RPM), sonicated in a bath sonicator for 10 minutes, and stirred for 10 minutes (500 RPM). The suspension containing the Si nanomaterials was evenly divided into two centrifuge bottles and recovered by centrifugation (Eppendorf 5810 centrifuge, 3900 RPM for 5 minutes). The supernatant was discarded, and the obtained Si nanomaterial was recovered. The recovered nanomaterial was suspended in 0.5% HF in methanol (10 mL of 48% HF (aqueous solution) in 990 mL of MeOH) by sonication in a bath sonicator (5 minutes), shaking on an orbital shaking table (MaxQ 2000, Thermo Scientific) (5 minutes), and sonication in a bath sonicator (10 minutes). The suspended nanomaterial was then recovered by centrifugation (5 minutes at 3900 RPM) by discarding the supernatant. Finally, the nanomaterial was suspended in Ar-purged toluene (900 mL) by sonication in a bath sonicator (5 minutes), shaking on an orbital shaking table (5 minutes), and sonication in a bath sonicator (10 minutes).
[0366] To immobilize 4-VBC and tBA, HF-treated Si nanomaterials suspended in toluene were evenly divided into glass bottles (250 mL, Labsolute) with four screw-cap lids equipped with a magnetic stirring bar, placed on a magnetic stirring plate, and stirred at 300 RPM. The tBA and 4-VBC were passed through an Al2O3 column. The Bluecap bottles were closed with a diaphragm while maintaining an argon flow within the bottles.
[0367] Different amounts of tBA and 4-VBC with 4-decylbenzyl diazonium tetrafluoroborate (416 mg in each reaction) Table 1 As shown in [figure], it was added to reactions 1 to 4.
[0368] Table 1 Overview of the experimental structure and reaction mixture composition regarding the concentrations and relative ratios of two co-grafted reactive species.
[0369]
[0370] After 2 hours, the suspended particles were transferred to centrifuge bottles and recovered by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and the nanomaterials were resuspended by adding 25 mL of DCM to each centrifuge bottle. The bottles were sonicated in a bath sonicator for 10 minutes and shaken on an orbital shaker until the Si nanomaterials were well resuspended. Subsequently, 250 mL of methanol was added to each centrifuge bottle, followed by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and the steps of DCM suspension, MeOH addition, and centrifugation were repeated once more. The Si nanomaterials were then dried to obtain the final product.
[0371] A reaction that immobilizes only 4-vinylbenzyl chloride ( Table 1Reaction No. 5) was performed using 20 g of HF-treated Si nanomaterials suspended in 1000 mL of toluene. 142.5 mL of vinylbenzyl chloride was added by passing it through an Al2O3 column. While maintaining the reaction under an argon flow, 4-decylbenzyl diazonium tetrafluoroborate (1667.1 mg) was added. After 2 hours, the suspended nanomaterials were transferred to two centrifuge bottles and recovered by centrifugation (5 min at 3900 RPM). The supernatant was discarded, and the nanomaterials were resuspended by adding 50 mL of DCM to each centrifuge bottle; the bottles were sonicated in a bath sonicator for 10 minutes and shaken on an orbital shaker until the Si nanomaterials were well resuspended. Subsequently, 500 mL of methanol was added to each of the two centrifuge bottles, followed by centrifugation (5 min at 3900 RPM). The supernatant was discarded, and the steps of DCM suspension, MeOH addition, and centrifugation were repeated once more. The Si nanomaterial was then dried to obtain the final product.
[0372] Fourier transform infrared spectroscopy (FTIR spectroscopy) was used to determine the ratio of 4-VBC and tBA immobilized on the surface. A Spectrum Two (PerkinElmer) instrument was used.
[0373] The FTIR peaks obtained upon immobilization of 4-VBC and tBA on Si particles include the peaks specified in Table 2 below:
[0374] Table 2: FTIR peak designation for spectra obtained by co-graphing tBA and 4-VBC.
[0375]
[0376] Above Table 2The peaks listed in [Figure 2] are integrated, as can be seen in [Figure 2], and the relative density of each molecule is obtained by normalizing each obtained peak area to the peak area obtained for particles decorated with the pure compound (i.e., decorated with tBA alone or 4-VBC alone). Since multiple peaks are integrated for both tBA (three distinct peaks) and 4-VBC (two distinct peaks), several series of relative density is obtained. To provide the most representative perspective of the data, the average of these series is taken and used to represent the relative amount of each immobilized molecule.
[0377] For this co-immobilized reagent set, several additional experiments were performed, and the concentrations, relative reagent amounts, and ratios for all experiments are provided in Table 3.
[0378] Table 3 : Experimental overview of the co-grafting of tert-butyl acrylate and quaternary-vinylbenzyl chloride for the spectrum shown in Fig. 2.
[0379]
[0380] Table 3 FTIR data obtained based on the experiments listed in were analyzed as described above, and the averaged of 4-vinylbenzyl chloride Relative surface stoichiometry silver It was decided as, and here tBA's Relative grafting density And, is the relative grafting density of 4-VBC.
[0381] relative density is subsequently averaged for each moiety precursor Relative surface stoichiometry It was used to calculate.
[0382] 4-VBC's Relative surface stoichiometry The study by Faucheux et al. describing two types of grafting with different rate constants on surfaces having reactive sites consumed during the grafting of silver molecules (literature[" LangmuirFitted with an expression based on [see 2006, 22, 1, 153-162]). Refer to the following equations:
[0383]
[0384] Here, n1 and n2 are species 1 and 2. Relative grafting density It represents, and therefore ε is the relative surface stoichiometry of species 2, k1 and k2 are the reaction rate constants for the surfaces of species 1 and 2, and c2 is the fraction of reactive species 2 in the reaction mixture (i.e., the proportion provided in the far right column of Table 2).
[0385] Figure 3 shows the fitting of the experimental data and the analytical expression, and the data from the fitting Table 4 It is collected in.
[0386] Table 4 : Values of fitted parameters (k1, k2), relative reaction rates, R-squared values for the fit, and p-values for the fitted model.
[0387]
[0388] Table 4 As is evident, 4-VBC reacts slightly faster than tert-butyl acrylate, considering its higher relative rate constant.
[0389] Example 2: Formation of a polymer brush on composite particles
[0390] A tBA-based polymer brush was grafted from decorated Si particles using a reaction composition containing 4-VBC / tBA in a 10:90 ratio ( Table 1 The product of reaction number 4 visible in).
[0391] Decorated Si particles using a reaction composition containing 4-VBC / tBA in a 10:90 ratio ( Table 13.08 g of reaction number 4) and 129 mL of isopropanol (iPrOH) were added to a glass vial containing a magnetic stirring bar. The contents were stirred for 10 minutes and sonicated in a bath sonicator for 10 minutes. Subsequently, tertiary-butyl methacrylate (18 mL), deactivated polymerization catalyst (7.49 mL), and DI water (85.9 mL) were added to the flask, and the contents were purged with argon for 8 minutes. In a separate glass flask sealed with a diaphragm, ascorbic acid (108.5 mg) and sodium ascorbate (842.4 mg) were mixed under an argon blanket. Subsequently, argon-purged deionized water (DI water) (3.6 mL) was transferred via a syringe to the flask containing ascorbic acid and sodium ascorbate, and the flask was shaken until the solids were dissolved. The solution of ascorbic acid and sodium ascorbate was subsequently transferred to a flask containing a particle suspension to activate the polymerization reaction. Over 60 minutes, the flask containing the polymerization reaction was sequentially subjected to sonication for 10 minutes and stirring for 10 minutes, resulting in a total of 30 minutes of sonication and 30 minutes of stirring.
[0392] The polymer brush particles were subsequently recovered by centrifugation (5 minutes at 3900 RPM), the supernatant was decanted and discarded, and the obtained polymer brush modified nanomaterial was placed on an orbital shaker for 10 minutes and sonicated in a bath sonicator for 5 minutes to be resuspended in dichloromethane (40 mL). MeOH (400 mL) was then added to the suspended particles and subsequently recovered by centrifugation (5 minutes at 3900 RPM). This step was repeated a total of two times. The obtained polymer brush modified nanomaterial was subsequently dried at ambient air at room temperature for 16 hours, then placed in a standard oven at 60°C for 90 minutes, and the product was obtained (3.68 g).
[0393] When forming a tBMA-based polymer brush, the tertiary-butyl group is removed, revealing a methacrylic acid-based polymer brush.
[0394] 2.97 g of the formed product was stirred for 10 minutes and sonicated in a bath sonicator for 10 minutes to be suspended in dichloromethane (149 mL). Methanesulfonic acid (0.39 mL) was added and the suspension was stirred for 2 hours. The Si nanomaterial was recovered by centrifugation (5 minutes at 3900 RPM), resuspended in DCM (160 mL) by sonication for 10 minutes, and recovered by centrifugation (5 minutes at 3900 RPM). This step was repeated twice to obtain the final product.
[0395] Subsequently, particles without polymer brushes, particles with tBMA polymer brushes, and particles with methacrylic acid (MAA) polymer brushes were subjected to thermogravimetric analysis (TGA).
[0396] As shown in Figure 4, thermogravimetric analysis (TGA) indicates the formation of poly(tert-butyl methacrylate) PB containing an organic fraction of 31 wt.%, and the organic mass fraction decreases to 21 wt.% due to mass loss from the removed tert-butyl groups resulting from the removal of the tert-butyl methacrylate groups. It should be noted that the organic fraction of the composite particles without polymer brushes is close to 0 wt.%, indicating a monolayer-like structure prior to PB formation.
[0397] In addition, ATR FTIR measurements were performed on particles having polymer brushes based on tBMA and MAA. The FTIR transmission spectra can be seen in Fig. 5, where the top line corresponds to the spectrum from particles having polymer brushes based on methacrylic acid, and the bottom line corresponds to the spectrum from particles having polymer brushes based on tBMA.
[0398] Peak designation is as follows Table 5 It is depicted in.
[0399] Table 5 : ATR FTIR peak designation for PtBMA and PMAA PB grown from particles decorated with a 90:10 ratio tBA / 4-VBC solution.
[0400]
[0401] ATR FTIR measurements further support the formation of PB from decorated Si particles using a solution containing tBA and 4-VBC.
[0402] Example 3: Co-immobilization of 4-vinylbenzyl chloride and pentafluorostyrene
[0403] The composite particles were decorated using 4-vinylbenzyl chloride (4-VBC) and penta-fluorostyrene (PFS) as first and second moiety precursors.
[0404] First, Si particles were treated with HF to form H-terminal Si surfaces:
[0405] 0.5 g of silicon nanomaterial (SkySpring Nanomaterials, D50 = 100 nm) was filled into each of four screw-cap polypropylene tubes equipped with magnetic stirring rods. Methanol (23 mL) was added to each tube, the contents were stirred for 10 minutes, and sonicated in a bath sonicator for 10 minutes. The suspension was returned to the stirring plate, and hydrofluoric acid (2 mL) was added to each screw-cap tube. The contents of the screw-cap tubes were then stirred for 10 minutes (500 RPM), sonicated in a bath sonicator for 10 minutes, and stirred for 10 minutes (500 RPM). The HF-treated Si nanomaterial was recovered by centrifugation (Eppendorf 5810 centrifuge, 3900 RPM for 5 minutes). The supernatant was discarded, and the obtained Si nanomaterial was recovered. In four separate screw-cap vials, the recovered nanomaterials were suspended in 25 mL of 0.5% HF in methanol (1 mL of 48% HF (aqueous solution) in 99 mL of MeOH) by sonication in a bath sonicator (5 min), shaking on an orbital shaking table (MaxQ 2000, Thermo Scientific) (5 min), and sonication in a bath sonicator (10 min). The suspended nanomaterials were then recovered by centrifugation (5 min at 3900 RPM) by discarding the supernatant. Finally, the nanomaterials were suspended in argon-purged toluene (25 mL in each of the four separate tubes) by sonication in a bath sonicator (5 min), shaking on an orbital shaking table (5 min), and sonication in a bath sonicator (10 min), thereby forming four screw-cap tubes each containing HF-treated Si nanomaterials suspended in toluene (25 mL).
[0406] Four screw-cap vials, each containing HF-treated Si nanomaterials suspended in argon-purged toluene (25 mL), were equipped with magnetic stirring rods, placed on a magnetic stirring plate, and stirred at 300 RPM. PFS and 4-VBC were passed through an Al2O3 column. The vials were closed with septa while maintaining an Ar flow within the vials. 4-VBC and PFS were added to the four screw-cap vials along with 4-decylbenzyl diazonium tetrafluoroborate (41.6 mg in each reaction) according to Table 6 (reaction numbers 1-4).
[0407] Table 6 : Reagent concentrations for PFS and 4-VBC co-grafting experiments.
[0408]
[0409] After 2 hours, the suspended nanomaterial was recovered by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and 2.5 mL of DCM was added to each screw-cap vial. The nanomaterial was sonicated in a bath sonicator for 10 minutes and resuspended by shaking on an orbital shaker until the Si nanomaterial was well resuspended. Subsequently, 25 mL of MeOH was added to each of the four screw-cap vials, followed by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and the steps of DCM suspension, MeOH addition, and centrifugation were repeated once more. The Si nanomaterial was then dried to obtain the final product.
[0410] Using the same procedure, particles decorated solely with 4-VBC were manufactured ( Table 6 Reaction number 5).
[0411] Table 6 Under the conditions shown, the co-immobilization of pentafluorostyrene (PFS) and 4-VBC resulted in the spectral data shown in Fig. 6a. From the top curve to the bottom curve, the products of reaction numbers 1, 2, 3, and 4, and finally the product of the reaction in which the particles were decorated solely with 4-VBC are seen.
[0412] Here, the analysis of the peak area is 1475 to 1550 cm² -1 It is performed on the peaks found in the aromatic region.
[0413] As shown in Fig. 6b, which is an enlarged view of Fig. 6a, pure 4-VBC is 1513 cm in this region. -1 While it has a single peak at , PFS has peaks at 1504 and 1523 cm⁻¹. -1 It shows two peaks.
[0414] These peaks are specified in Table 7 below:
[0415] Table 7 : FTIR peak designation for spectra obtained by co-graphing 4-VBC and PFS.
[0416]
[0417] Since three peaks overlap, peak fitting was used to obtain the relative density and relative surface stoichiometry of the two moiety.
[0418] Figure 7 shows an example of data fitting, here for PFS / 4-VBC with a 30:70 ratio. The raw data is fitted into a total of three components, one for each peak listed in Table 7.
[0419] Subsequently, the density of each of the two moietyes can be calculated at various ratios. Afterwards, Relative surface stoichiometry and Relative grafting density It can be calculated as shown in Example 1.
[0420] Figure 8 shows the relative surface stoichiometry of 4-VBC as a function of the fraction of 4-VBC in solution, determined in the same manner as described for the co-graphing of tBA and 4-VBC in the previous section.
[0421] The data was fitted to the same equation mentioned in Example 1 to arrive at the following data:
[0422] Table 8 : Values of fitted parameters (k1, k2), relative reaction rate (k2 / k1), R-squared value for the fit, and p-value for the fitted model.
[0423]
[0424] Table 8 The figure shows the data obtained by fitting the model to the data, indicating that 4-VBC responds about twice as fast as PFS.
[0425] Example 4: Formation of a polymer brush on composite particles
[0426] A polymer brush based on tertiary-butyl methacrylate was grafted from decorated Si particles using a reaction composition containing 4-VBC / PFS in a 50:50 ratio (of Example 3). Table 6 The product of reaction number 2 visible in).
[0427] Using a reaction composition containing 4-VBC / PFS in a 50:50 ratio, 297 mg of decorated particles and iPrOH (17.5 mL) were added to a screw-cap glass vial containing a magnetic stirring bar. The contents were stirred for 10 minutes and sonicated in a bath sonicator for 10 minutes. Subsequently, tertiary-butyl methacrylate (1.9 mL), deactivated polymerization catalyst (0.8 mL), and DI water (4.9 mL) were added to the flask. In a separate glass vial sealed with a septum, sodium ascorbate (103 mg) and DI water (0.4 mL) were mixed, and the vial was shaken until the solids were dissolved. The solution of sodium ascorbate was then transferred to a flask containing the particle suspension to activate the polymerization reaction. Over a period of 40 minutes, the flask containing the polymerization reaction was sequentially subjected to sonication for 10 minutes and stirred for 10 minutes, resulting in a total of 20 minutes of sonication and 20 minutes of stirring.
[0428] The polymer brush particles were subsequently recovered by centrifugation (5 minutes at 3900 RPM), the supernatant was decanted and discarded, and the obtained polymer brush nanomaterial was placed on an orbital shaker for 10 minutes and sonicated in a bath sonicator for 5 minutes to be resuspended in dichloromethane (4 mL). MeOH (40 mL) was then added to the suspended particles and subsequently recovered by centrifugation (5 minutes at 3900 RPM). This step was repeated a total of two times. The obtained polymer brush nanomaterial was subsequently dried at ambient air at room temperature for 16 hours, and the final product was obtained (317 mg).
[0429] When forming a tBMA-based polymer brush, the tertiary-butyl group is removed, and an MAA-based polymer brush can be revealed by the following method:
[0430] 317 mg of Si nanoparticles decorated with PFS and 4-VBC, from which PtBMA polymer brushes were formed, were suspended in dichloromethane (17.5 mL) by stirring for 10 minutes and sonicating in a bath sonicator for 10 minutes. Methanesulfonic acid (44.5 μL) was added for deprotection, and the suspension was stirred for 2 hours. The Si nanomaterial was recovered by centrifugation (5 minutes at 3900 RPM), resuspended in DCM (25 mL) by sonication for 10 minutes, and recovered by centrifugation (5 minutes at 3900 RPM). This step was repeated twice to obtain the final product.
[0431] Subsequently, particles without polymer brushes, particles with tertiary-butyl methacrylate polymer brushes, and particles with methacrylic acid polymer brushes underwent thermogravimetric analysis (TGA).
[0432] As shown in Figure 9, thermogravimetric analysis (TGA) indicates the formation of poly(tert-butyl methacrylate) PB with an organic fraction of 43 wt%, and the organic mass fraction reduced to 30 wt% due to the removal of the tert-butyl methacrylate group.
[0433] In addition, KBr FTIR measurements were performed on Si nanomaterials decorated with 4-VBC / PFS, the same material in which a PtBMA polymer brush was grown from the VBC-initiation site, and the same material with a PMAA polymer brush.
[0434] The FTIR transmission spectra can be seen in Fig. 10, where the top line corresponds to the spectrum from particles with a methacrylic acid-based polymer brush, the bottom line corresponds to the spectrum from particles with a tBMA-based polymer brush, and the bottom line corresponds to particles before the polymer brush formation.
[0435] Peak designation is as follows Table 9 It is depicted in.
[0436] Table 9 : Peak designation for the data shown in Fig. 10.
[0437]
[0438] This shows that tertiary-butyl groups can be removed from the polymer brush to expose the PMAA polymer brush, and as a result, a fluorinated hydrophobic layer and a hydrophilic polymer brush structure are formed.
[0439] Example 5: Co-immobilization of 4-VBC and acrylonitrile
[0440] The composite particles were decorated using 4-VBC and acrylonitrile (AN) as first and second moiety precursors.
[0441] First, Si particles were treated with HF to form an H-terminal Si surface using the procedure seen in Example 3.
[0442] Four screw-cap vials, each containing HF-treated Si nanomaterials suspended in argon-purged toluene (25 mL), were equipped with magnetic stirring rods, placed on a magnetic stirring plate, and stirred at 300 RPM. 4-VBC and AN were passed through an Al2O3 column. The screw-cap vials were closed with septa while maintaining an Ar flow within the vials. 4-VBC and AN were added to the four screw-cap vials along with 4-decylbenzyl diazonium tetrafluoroborate (41.6 mg in each reaction) according to Table 10.
[0443] Table 10 : Reagent concentrations for AN and 4-VBC co-grafting experiments.
[0444]
[0445] 0.082 mL of acrylonitrile was measured by taking 0.82 mL from a 10% (by volume) solution of acrylonitrile in toluene. 0.0082 mL of acrylonitrile was measured by taking 82 μL from a 10% (by volume) solution of acrylonitrile in toluene.
[0446] After 2 hours, the suspended nanomaterial was recovered by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and 2.5 mL of DCM was added to each screw-cap vial. The nanomaterial was sonicated in a bath sonicator for 10 minutes and resuspended by shaking on an orbital shaker until the Si nanomaterial was well resuspended. Subsequently, 25 mL of methanol was added to each of the four screw-cap vials, followed by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and the steps of DCM suspension, MeOH addition, and centrifugation were repeated once more. The Si nanomaterial was then dried to obtain the final product.
[0447] Using the same procedure, particles decorated with only 4-VBC were manufactured.
[0448] Co-graphing of AN and 4-VBC under the conditions shown in Table 10 resulted in the spectral data shown in Fig. 11, where the curve number corresponds to the reaction number in Table 10. Here, the analysis of peak area is performed for the peaks listed in Table 11.
[0449] Table 11 : FTIR peak designation for spectra obtained by co-graphing 4-VBC and AN.
[0450]
[0451] Subsequently, the density of each of the two moietyes can be calculated at various ratios. Afterwards, Relative surface stoichiometry and Relative grafting density It can be calculated as shown in Example 1.
[0452] Figure 12 shows the relative surface stoichiometry of 4-VBC as a function of the fraction of 4-VBC in solution, determined in the same manner as described for the co-graphing of tBA and 4-VBC in the previous section.
[0453] The data is fitted to the same equation as mentioned in Example 1. Table 12 The following data visible in has been reached:
[0454] Table 12 : Values of fitted parameters (k1, k2), relative reaction rate (k2 / k1), R-squared value for the fitting, and p-value for the fitted model shown in FIG. 12.
[0455]
[0456] Table 12 is 471 cm for AN -1 , for 4-VBC, 1513 and 3026 cm -1 The data obtained by fitting a model to the data from the peak is shown. AN appears to react about 2.5 times faster than 4-VBC.
[0457] Comparative Example 6: Co-immobilization of 4-VBC and allylamine
[0458] The composite particles were decorated using 4-VBC and A) as first and second moiety precursors.
[0459] First, Si particles were treated with HF to form an H-terminal Si surface using the procedure seen in Example 3.
[0460] Four screw-cap vials, each containing HF-treated Si nanomaterials suspended in argon-purged toluene (25 mL), were equipped with magnetic stirring rods, placed on a magnetic stirring plate, and stirred at 300 RPM. 5 mL of 4-vinylbenzyl chloride and 5 mL of allylamine were passed through an Al2O3 column. The screw-cap vials were closed with septa while maintaining an argon flow within the vials. 4-VBC and allylamine were combined with 4-decylbenzyl diazonium tetrafluoroborate (41.6 mg in each reaction). Table 13 It was added to four screw-cap vials according to the above.
[0461] Table 13 : Reagent concentrations for allylamine and 4-VBC co-grafting experiments.
[0462]
[0463] 0.09 mL of allylamine was measured by taking 0.9 mL from a 10% (by volume) solution of allylamine in toluene.
[0464] After 2 hours, the suspended nanomaterial was recovered by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and 2.5 mL of DCM was added to each screw-cap vial. The nanomaterial was sonicated in a bath sonicator for 10 minutes and resuspended by shaking on an orbital shaker until the Si nanomaterial was well resuspended. Subsequently, 25 mL of MeOH was added to each of the four screw-cap vials, followed by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and the steps of DCM suspension, MeOH addition, and centrifugation were repeated once more. The Si nanomaterial was then dried to obtain the final product.
[0465] Table 13 Under the conditions shown, co-immobilization of allylamine and 4-VBC did not proceed.
[0466] Notably, even at a 10:90 ratio of allylamine to 4-VBC, no peak for 4-VBC is observed in any of the obtained spectra.
[0467] Therefore, this experiment demonstrates the limitations of chemical functional groups that can be used in this methodology, showing that not only is it possible that allylamine cannot be grafted onto the surface, but it also hinders the grafting of another molecule (4-VBC) known to be grafted under different conditions.
[0468] Example 7: Control of 4-VBC grafting density by lowering the concentration of 4-VBC in the reaction mixture.
[0469] All of the above examples (i.e., Examples 1-6) were designed to control the density of 4-VBC by diluting with another reactive molecule during the hydrosilylation reaction. However, lowering the concentration of 4-VBC without adding another co-grafting agent can also reduce the amount of grafted material, as can be seen below.
[0470] Use the procedure of Example 1, but as follows: Table 14Si particles were decorated by adding only one type of moiety, namely 4-VBC, at the concentration specified in:
[0471] Table 14 : Concentration evaluated for density control using only one reactant, 4-vinylbenzyl chloride.
[0472]
[0473] Figure 13 shows the FTIR spectrum, and Figure 14 shows the correlation between the peak area from 4-VBC and the solution concentration of 4-VBC. The peak corresponding to 4-VBC ( Table 2 (Reference) was analyzed in the FTIR spectrum. The normalized peak area was plotted against the 4-VBC concentration, as can be seen in Fig. 14.
[0474] Example 8: Immobilization of tBA as a protected carboxylic acid, and subsequent de-tertiary-butylation to expose the carboxylic acid
[0475] This example illustrates a method in which particles can be decorated with protic groups (carboxylic acids) despite the incompatibility of protic species, such as allylamine, shown in Comparative Example 6, and the hydrosilylation reaction.
[0476] First, Si particles were treated with HF to form an H-terminal Si surface using the procedure seen in Example 1.
[0477] HF-treated Si nanomaterials were suspended in 200 mL of argon-purged toluene (corresponding to a starting mass of 4 g of Si nanomaterials), placed in a flask, and stirred with a magnetic stirring bar. tBA was passed through an Al2O3 column, and 14.71 mL of tBA was added to the flask along with 333.2 mg of 4-decylbenzenediazonium tetrafluoroborate.
[0478] After 2 hours, the nanomaterial was recovered by centrifugation (5 minutes at 3900 RPM), and the following purification step was repeated twice: the supernatant was decanted, the particles were sonicated in a bath sonicator for at least 10 minutes to resuspend them in 200 mL of toluene, and then the Si nanomaterial was recovered by centrifugation (5 minutes at 3900 RPM).
[0479] After the immobilization (covalent bonding) of tBA, the de-tertiary-butylation reaction can be achieved using the following method:
[0480] The nanomaterial was resuspended in 200 mL of DCM by stirring with a magnetic stirring bar for 15 minutes. 1.56 mL of methanesulfonic acid was added, and after 20 hours, the Si nanomaterial was recovered by centrifugation, and the following purification routine was repeated twice: the supernatant was discarded, and the Si nanomaterial was sonicated in a bath sonicator for 10 minutes and resuspended in 300 mL of DCM. The Si nanomaterial was subsequently recovered by centrifugation (5 minutes at 3900 RPM) and dried.
[0481] Figures 15a and 15b show the KBr FTIR spectra obtained after grafting tBA and after removing the tertiary-butyl group, respectively. The exposure of the carboxylic acid simultaneously with the removal of the tertiary-butyl group is indicated by the 1366 cm⁻¹ junction specified for the tertiary-butyl CH₄ bend. -1 Disappearance of the peak at and 2500 to 3600 cm⁻¹ -1 This is evident from the presence of a broad peak. 3rd- 3000 to 3600 cm before removal of butyl group -1 The broad peak in between is attributed to water bound to KBr (Reference [Socrates, G., Infrared and Raman Characteristic Group Frequencies - Tables and Charts, 3 rd According to [Edition, John Wiley and Sons]).
[0482] This demonstrates a method in which proton paper can be grafted onto a surface through the use of protecting group chemistry, which is a tertiary-butyl ester, in this case.
[0483] Example 9: Particle Size
[0484] The sizes of Si nanomaterials decorated with 4-VBC, the same material in which PtBMA PB was grown from Si nanomaterials decorated with 4-VBC, and the same material with PMAA polymer brushes were evaluated using dynamic light scattering.
[0485] First, Si particles were treated with HF to form an H-terminal Si surface using the procedure seen in Example 3.
[0486] A screw-cap bottle containing HF-treated Si nanomaterials suspended in argon-purged toluene (25 mL) was placed on a magnetic stirring plate and stirred at 300 RPM. 5 mL of 4-vinylbenzyl chloride was passed through an Al2O3 column. The screw-cap bottle was closed with a diaphragm while maintaining an argon flow within the reactor. 1.78 mL of 4-VBC was added to the reaction along with 4-decylbenzyl diazonium tetra-fluoroborate (41.4 mg). After 2 hours, the suspended nanomaterials were recovered by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and the nanomaterials were resuspended by adding 25 mL of toluene to the centrifuge bottle, sonicating in a bath sonicator for 10 minutes, and shaking on an orbital shaker until the Si nanomaterials were well resuspended. The Si nanomaterial was recovered by centrifugation (5 minutes at 3900 RPM), the supernatant was discarded, and the toluene suspension and centrifugation steps were repeated once more, after which the same purification routine was performed twice using isopropanol as a solvent. The obtained material was used directly in the following polymer brush formation reaction.
[0487] Subsequently, the polymer brush was formed using the following methodology:
[0488] The 4-VBC modified Si nanomaterials were sonicated for 10 minutes and resuspended in 17.5 mL of iPrOH; the reaction vessel was equipped with a magnetic stirring bar and transferred to a stirring plate. 4.9 mL of deionized water, 1.9 mL of tBA, and 0.78 mL of deactivated polymerization catalyst were added to the stirred particle suspension. 100 mg of NaAsc dissolved in 0.4 mL of deionized water was added to the stirred particle suspension, followed by sequential sonication and stirring in 10-minute intervals for a total of 40 minutes. The polymer brush modified Si nanomaterials were subsequently recovered by centrifugation (5 minutes at 3900 RPM) and purified by performing the following steps twice: the supernatant was discarded, the Si nanomaterials were sonicated for 5 minutes and resuspended in 4 mL of DCM, 10 mL of diethyl ether was added, and the nanomaterials were recovered by centrifugation (5 minutes at 3900 RPM).
[0489] Finally, the tertiary-butyl group was removed to reveal the PMAA polymer brush:
[0490] The PtBMA-modified Si nanomaterial was resuspended in 25 mL of DCM by sonication (10 min) and stirred for 5 minutes. 195 μL of methanesulfonic acid was added to the particle suspension. After 20 hours, the Si nanomaterial was recovered by centrifugation (5 min at 3900 RPM) and purified by repeating the following steps twice: the supernatant was decanted, the Si nanomaterial was resuspended in DCM (25 mL), and then recovered by centrifugation (5 min at 3900 RPM).
[0491] Figure 16 illustrates the variation in particle size distribution determined by dynamic light scattering (DLS) measurements. Each curve is numbered as described below:
[0492] - Size distribution of "pure" Si nanomaterials (suspension in MeOH, curve number 1)
[0493] - Size distribution of 4-VBC after grafting (suspension in iPrOH, curve number 2)
[0494] - Size distribution after PtBMA polymer brush formation (suspension in DCM, curve number 3)
[0495] - To expose the PMAA polymer brush 3rd- Size distribution after removal of butyl protecting group (suspension in MeOH, curve number 4)
[0496] Corresponding D 50 The particle size is as follows Table 15 You can check it at.
[0497] Table 15. D for different stages of the Si nanomaterial deformation process 50 (nm) particle size.
[0498]
[0499] Apparently, forming a thin organic layer on the surface of Si nanomaterials by combining ultrasonic treatment, HF etching, and 4-VBC grafting results in smaller particles and lower D compared to "as-is" nanomaterials. 50 A is obtained, which appears to be because the process crushes aggregates present in the material as obtained. After the formation of the polymer brush, D 50 increases significantly, indicating the formation of a thicker organic layer. Finally, after the removal of the protecting group, the particle size distribution and D 50 It decreases, which corresponds to the lower molecular mass of the polymer's repeating units, and therefore a thinner polymer brush layer.
[0500] Figure 17 shows the FTIR spectrum obtained after removing the tertiary-butyl group to confirm the chemical identity of the polymer brush on the Si nanomaterial. Table 9By comparison with the peaks listed and specified, the large band at 1699 cm-1 indicates the presence of a C=O carbonyl functional group from the carboxylic acid, whereas the absence of the sharp peak at 1366 cm-1 indicates the complete removal of the tertiary-butyl group. The broad peak at 2500–3600 cm-1 also indicates the presence of the carboxylic acid.
[0501] Example 10: SiO throughout an exemplary grafting process x and changes in Si-H amount
[0502] This example describes the amounts of SiOx and Si-H bonds present after an exemplary "raw" Si nanomaterial, an HF-treated Si nanomaterial, and a hydrosilylation reaction with 100% tertiary-butyl acrylate.
[0503] Si particles were treated with HF to form an H-terminal Si surface using the procedure seen in Example 3.
[0504] HF-treated Si nanomaterials suspended in argon-purged toluene (25 mL) were placed on a magnetic stirring plate and stirred at 300 RPM. 5 mL of tBA was passed through an Al2O3 column. A screw-cap bottle was closed with a diaphragm while maintaining an argon flow within the reactor. 1.84 mL of tBA was added to the reaction along with 4-decylbenzyl diazonium tetrafluoroborate (41.2 mg). After 2 hours, the suspended nanomaterials were recovered by centrifugation (5 minutes at 3900 RPM). The supernatant was discarded, and the nanomaterials were resuspended by adding 25 mL of toluene to the centrifuge bottle, sonicating in a bath sonicator for 10 minutes, and shaking on an orbital shaker until the Si nanomaterials were well resuspended. The Si nanomaterials were recovered by centrifugation (5 minutes at 3900 RPM), the supernatant was discarded, and the toluene suspension and centrifugation steps were repeated once more; subsequently, the Si nanomaterials were dried under an argon flow in a vessel under an inert atmosphere. After drying, a small amount of the sample contained Si-H and SiOx It was immediately prepared into KBr pellets to measure the content.
[0505] Figure 18a shows the full FTIR spectra of untreated Si nanomaterials, HF-etched Si nanomaterials, and the same material after a diazonium-initiated hydrosilylation reaction with 100% tertiary-butyl acrylate to completely decorate the particles with tBA.
[0506] 800 to 1300 cm -1 The large peak in the range is edited based on literature reports [Saputra RE et al., Molecular and Biomolecular spectroscopy 199 (2018) 12-20; Sun, XH, et al. Inorganic chemistry, 42, 2003, 2399; Mawhinney, DB, et al., J. Phys. Chem. B, 1997, 101, 1202-1206] Table 16 This is a composite peak for a series of Si-O-Si and Si-OH species according to (below).
[0507] Table 16 : SiO x Peak designation for the species.
[0508]
[0509] Various SiO in Fig. 18b x H 4-x The peak is designated for HF-treated Si nanomaterials and ranges from the most reduced SiH3 species to more oxidized species such as SiH(O)3, SiH2(O)2, and SiH(O)2. x H 4-x It indicates the presence of species. Plotted together in Figs. 18a and 18b is the KBr FTIR after the hydrosilylation reaction, which in this case shows a reduced amount of the Si-H band after the reaction, consistent with their reaction with the grafting agent tBA.
[0510] By normalizing KBr FTIR intensity to the Si sample mass and subsequently integrating the peaks, Si-H and SiO are obtained as the Si nanomaterial undergoes processing ("as is," HF-etching, hydrosilylation reaction). x You can determine the relative amount of.
[0511] As shown by the data in Table 17, the SiO initially present after HF treatment x Only 6.3% of the peak area remains, which indicates almost complete removal of SiOx species during HF treatment.
[0512] Table 17 : Peak areas of Si-H and SiOx species immediately after HF etching and after the subsequent hydrosilylation reaction with 100% tertiary-butyl acrylate.
[0513]
[0514] To determine the amount of Si-H bands reacting during the hydrosilylation reaction, the peak area for HF-treated Si nanomaterials and the same material after hydrosilylation is determined. Table 17 As shown by the exemplary data, the Si-H peak area after the hydrosilylation reaction It disappears, indicating that some Si-H species remain after the reaction, which is expected based on steric considerations, namely that the distance is greater than the distance between the two nearest Si-H bands to which the grafted molecule could have reacted.
[0515] Example 11: Qualitative observations regarding the stability of HF-treated Si nanomaterials and Si nanomaterials modified with a polymer brush.
[0516] Si-Si bonds are known to be unstable and reactive to oxidation through reaction with water and / or ambient oxygen.
[0517] The surface is SiO xA stabilization effect is observed when the surface is covered with a layer, but when the surface is Si-H terminaled after HF treatment, a violent reaction between the Si nanomaterial and water can be observed. Specifically, when Si-H terminaled Si nanomaterials obtained through HF treatment are mixed with water, gas bubble formation is observed from the redox reaction between the Si-Si bond and water, and H2 gas is formed.
[0518] This contrasts with observations made when Si nanomaterials modified with a PMAA polymer brush are mixed with water; in this case, no spontaneous gas generation is observed, indicating that the polymer brush has a stabilizing effect on the Si nanomaterials.
[0519] In fact, when modified into a PMAA polymer brush, the suspension of particles can be adjusted in pH from an initial value (just below pH 2 due to the carboxylic acid group) to a value of pH 7 by the addition of hydroxide ions without causing significant oxidation of the Si-Si bonds (Fig. 20).
[0520] This is indicated by the ATR FTIR spectrum in Fig. 19 showing the presence of the polymer brush after pH adjustment, and refer to Table 18 for peak designation.
[0521] Table 18. Peak designation for the ATR FTIR spectrum presented in Fig. 19.
[0522]
[0523] In the case of strong oxidation of Si-Si bonds, the particles were strongly oxidized, and it was observed that there were little to no polymer brush signals in the FTIR spectrum after the oxidation reaction. In some cases, for example, in a basic environment with pH > 7, the reaction with water was observed to be self-accelerating, with the vigorous reaction continuously exposing new Si-Si bonds, which were subsequently attacked by more water, leading to the breakdown of the Si nanomaterial. When the pH was adjusted to pH 7 in an acidic environment while the polymer brush was present on the Si nanomaterial, a peak related to the polymer brush layer still existed, indicating improved stability compared to HF-treated particles.
[0524] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as generally understood by those skilled in the art to which this disclosure pertains.
[0525] Example 12: Formation of a polymer brush on graphite powder.
[0526] In this embodiment, the inventors first show the covalent attachment of a polymerization initiator onto graphite particles, and then show the formation of a surface polymer grown from the covalently attached polymerization initiator. The graphite substrate was selected to have a well-defined system and demonstrates that a polymer brush can be formed from the surface of a carbonaceous material.
[0527] Attachment of polymerization initiator to graphite powder.
[0528] 139 g of graphite powder (SLC1520T, Superior Graphite) was suspended in DI water (1375 mL) in a flask by stirring with a magnetic stirrer at 1000 RPM for 10 minutes. The suspended graphite powder was then sonicated in a small sonicator for 10 minutes and returned to stirring at 600 RPM. 1654.6 mg of 4-(chloromethyl)benzenediazonium tetrafluoroborate (CBD) and 481.3 mg of sodium ascorbate were added, the flask was sealed, and left to be stirred for 150 minutes. After 150 minutes, 481.3 mg of sodium ascorbate was added, and the suspension was left to be stirred for an additional 150 minutes.
[0529] Subsequently, the graphite suspension was divided into two centrifuge bottles and centrifuged using an Eppendorf 5810 centrifuge at 3900 RPM for 5 minutes to recover the graphite. The supernatant was then decanted, and the graphite in each bottle was resuspended in 500 mL of DI water by shaking on a shaking plate for 10 minutes and sonicating for 10 minutes, and then shaken manually as needed to obtain a good suspension of graphite-I. This rinsing process was repeated twice with DI water and twice with acetone, after which the graphite was left to dry under ambient conditions, and the mass of the obtained product was 129 g. Graphite with a covalently attached polymerization initiator is designated as graphite-I.
[0530] Formation of a polymer brush from a polymerization initiator covalently attached to graphite particles.
[0531] Solution A, consisting of DI water (440.4 mL) and iPrOH (660.6 mL), was mixed in a bottle. 125 g of graphite-I (graphite powder with a covalently attached polymerization initiator as described above) was suspended in 367 mL of mixture A by stirring at 500 RPM for 10 minutes and then sonicating for 10 minutes. This resulted in the formation of a smooth and homogeneous suspension of graphite-I particles.
[0532] To form solution B, 633 mL of solution A was combined with a catalyst solution (0.28 mM) containing tertiary-butyl methacrylate (92.3 mL), Me6TREN (180 μL), DI water (38.4 mL), and Cu(II) (324 mg / L, obtained from a solid copper source) (38.4 mL). Sodium ascorbate (4920.3 mg) was dissolved in DI water (18.5 mL), and this sodium ascorbate solution was added to solution B, mixed, and left to stand for 5 minutes. After 5 minutes, the polymerization reaction was initiated by combining solution A and solution B and allowed to react for 30 minutes. The inventors observed that after 2 to 5 minutes of polymerization, the graphite particles began to aggregate to form larger particles, which is consistent with the formation of polymer chains that are significantly hydrophobic on the surface and leads to aggregation in an aqueous solvent. This strongly indicates the formation of covalently attached surface polymers on graphite particles.
[0533] After 30 minutes, graphite particles with covalently attached PtBMA polymer brushes were recovered by separating the graphite suspension into centrifuge bottles and centrifuging at 3900 RPM for 5 minutes. The supernatant was discarded, and the graphite in each centrifuge bottle was resuspended in 400 mL of DCM by shaking on a shaking plate (10 minutes) and sonicating (10 minutes), and shaking the bottles as needed to ensure a good suspension of graphite-PtBMA. This process of centrifugation, supernatant separation, and resuspension in DCM was repeated a total of three times, after which the graphite powder was left to dry under ambient conditions. The obtained material is referred to as graphite-PtBMA.
[0534] Conversion of PtBMA polymer brushes to PMAA polymer brushes
[0535] With the intention of controlling and demonstrating the binding of lithium ions in polymer brushes covalently attached to graphite particles, the inventors here demonstrate the conversion of a PtBMA polymer brush into a PMAA polymer brush through acid-catalyzed de-tertiary-butylation, i.e., the removal of a tertiary-butyl protecting group. This reaction will thus convert graphite-PtBMA into graphite-PMAA.
[0536] 117 g of graphite-PtBMA with covalently attached PtBMA polymer brushes was suspended in DCM (1250 mL) by stirring (500 RPM, 10 min) and sonicating for 10 min. This formed a smooth and homogeneous suspension, demonstrating the hydrophobic properties of the graphite particles imparted by the hydrophobic PtBMA polymer brushes. Subsequently, 1.625 mL of methanesulfonic acid was added to the stirred suspension of graphite with PtBMA polymer brushes to initiate the removal of tertiary-butyl protecting groups. Within 5 minutes, the inventors observed that the smooth suspension of graphite particles in the DCM began to form loose aggregates and larger particles. This is in good agreement with expected behavior, as the removal of tertiary-butyl groups leads to the formation of PMAA. The carboxylic acid functional groups of this polymer brush are known to form strong hydrogen bonds and dimers with other carboxylic acids, leading to interactions between individual graphite-PMAA particles and causing aggregation. In combination with the hydrophilic nature of the carboxylic acid functional groups and the hydrophobic DCM solvent, the formation of particles and aggregates demonstrates the rapid and efficient conversion of PtBMA polymer brushes to PMAA polymer brushes, accompanied by a simultaneous conversion of solubility and hydrophilicity. The graphite-PMAA suspension was divided into two centrifuge bottles and recovered by centrifugation at 3900 RPM for 5 minutes. The obtained supernatant was discarded, and the graphite-PMAA was resuspended in MeOH by adding 200 mL of MeOH to each centrifuge bottle, placing the bottle on a shaking plate for 10 minutes, and sonicating for 10 minutes. If necessary, the bottles were further shaken by hand to ensure a good suspension of the graphite-PMAA. After resuspending, the suspension was centrifuged again at 3900 RPM for 5 minutes, and the supernatant was discarded. This rinsing process was repeated three times, and the material was air-dried under ambient conditions to obtain a graphite-PMAA material.
[0537] Bonding of lithium ions to PMAA polymer brushes on graphite particles.
[0538] To bind lithium ions to a PMAA polymer brush to produce a poly(lithium methacrylate) polymer brush, the following procedure was performed.
[0539] DI water (1250 mL) was purged with argon for 45 minutes while stirring at 250 RPM. Then, graphite-PMAA (114.2 g) was added, and the suspension was stirred at 800 RPM for 60 minutes. Afterward, the suspension was sonicated for 10 minutes and stirred for an additional 10 minutes at 800 RPM. Then, lithium hydroxide monohydrate (LiOH, 5240 mg) was added, and the suspension was stirred for 60 minutes.
[0540] To recover graphite particles with poly(lithium methacrylate) (PMAA-Li) polymer brushes, the suspension was divided into two centrifuge bottles and centrifuged at 3900 RPM for 5 minutes. The supernatant was decanted, and 300 mL of DI water was added to each centrifuge bottle. The graphite particles with PMAA-Li polymer brushes (graphite-PMAA-Li) were subsequently Concussion plate The mixture was shaken (120 RPM, 10 min) and sonicated for 10 min, then centrifuged again to be resuspended. These steps were repeated twice, and the graphite powder with PMAA-Li polymer brushes was left to air dry under ambient conditions.
[0541] Data supporting surface polymer formation on graphite particles
[0542] The elemental composition of the graphite particle surface was determined by X-ray photoelectron spectroscopy (XPS) after each reaction, and chemical functional groups present in different materials were recorded using ATR IR spectroscopy.
[0543] Table 19 shows the elemental composition for each step determined by XPS measurements.
[0544] Table 19.Elemental composition of graphite particle surfaces after different process steps determined by XPS analysis.
[0545]
[0546] After producing graphite-I, an initiator-functionalized graphite, by attaching a polymerization initiator (CBD), 1.1 At% chlorine was detected, which is consistent with the presence of chlorine atoms within the polymerization initiator molecule that take the form of benzyl chloride after being attached to the graphite surface by covalent bonds. The low chlorine concentration is consistent with the formation of a thin layer of initiator on the surface of the graphite particles, as the polymerization initiator contains chloride atoms.
[0547] The formation of the PtBMA polymer brush resulted in a higher amount of oxygen (13.6 At%), which is consistent with the presence of oxygen in the polymer repeating unit (3 O atoms and 8 C atoms). C was observed at a higher ratio than the 8 C atoms to 3 O atoms ratio based on the polymer composition, which is due to the presence of a background signal from the graphite substrate contributing to the measured amount of C. The theoretical C:O ratio for PtBMA is 8:3, resulting in a theoretical ratio of 27.3 At% O and 72.7 At% C.
[0548] When graphite-PMAA is produced by removing the tertiary-butyl group, the amount of oxygen increases to 17.2 At%, which is consistent with fewer carbon atoms in the polymer brush, which now has a composition of 4 C atoms to 2 O atoms in the repeating unit, resulting in an expected theoretical composition of 66.6 At% C and 33.3 At% O. Again, the contribution of the C concentration in the graphite substrate explains the higher-than-expected C content.
[0549] Finally, exposure of graphite-PMAA to LiOH produces graphite-PMAA-Li, which is indicated by the presence of 9.4 At% lithium. Since the reaction between the carboxylic acid and LiOH is expected to result in the formation of lithium carboxylate, the oxygen-to-lithium ratio is expected to be 2:1, and the experimental data shows 18.6:9.4 = 1.98, which is in very good agreement with the theoretical composition of poly(lithium methacrylate) having 2 oxygen atoms per Li atom.
[0550] The chemical structure of the surface polymer on the graphite was further confirmed by ATR IR measurements presented in Fig. 24. Spectrum 1 in Fig. 24, corresponding to graphite-I, is largely featureless, which is consistent with a very thin layer of polymerization initiator below the instrument's detection limit. Spectrum 2 in Fig. 24, corresponding to graphite-PtBMA, is at 1716 cm⁻¹. -1 It exhibits a strong peak (Peak A in Fig. 24), which is due to the stretching of the ester carbonyl groups of the PtBMA surface polymer. Additionally, at 1366 cm⁻¹ -1 The sharp peak (peak D) at indicates the presence of a tertiary-butyl group and is assigned to the symmetric CH3 bending vibration of the tertiary-butyl group. 1000 cm⁻¹ -1 up to 1500 cm -1 The remaining peaks are a combination of CH bending vibrations, CO stretching vibrations, and CC skeletal vibrations, all consistent with the presence of PtBMA surface polymer.
[0551] When graphite-PtBMA is exposed to methanesulfonic acid in DCM to generate graphite-PMAA, a visible change is observed in the corresponding IR spectrum, Spectrum 3 in Fig. 24. Specifically, 1366 cm⁻¹ -1 The sharp peak at disappears, which is consistent with the removal of the tertiary-butyl group. Additionally, the position of the peak due to the C=O stretching vibration is 1689 cm⁻¹. -1It shifted to (peak C), indicating the presence of carboxylic acid. The C=O stretching peak also broadened, which is caused by hydrogen bonding between the formed carboxylic acid functional groups of the PMAA polymer brush.
[0552] Finally, in the case of graphite-PMAA-Li, the major change is the formation of lithium carboxylate, which is indicated by the C=O stretching peak at 1689 cm⁻¹ in Spectrum 4 of Fig. 24. -1 From 1542 cm -1 It appears as a shift to (peak C), which is consistent with the formation of metal carboxylate functional groups due to the reaction of the carboxylic acid functional groups of the PMAA surface polymer with LiOH, resulting in the formation of PMAA-Li polymer brushes.
[0553] Example 13: Attachment of polymerization initiator to Cu.
[0554] This example describes a procedure for cleaning and attaching a polymerization initiator on a copper sample suitable for a battery electrode.
[0555] Before the attachment of the polymerization initiator, the sample is cleaned as follows:
[0556] In the reaction vessel, H2SO4 (1 mL) is added to DI water (99 mL). Six Cu samples (20x20x7 mm) are flushed in iPrOH, dried, and placed in the reaction vessel. The H2SO4 solution is poured into the reaction vessel, and the system is left for 5 minutes. The samples are removed from the solution, flushed in DI water, placed in a container of DI water, and sonicated for 5 minutes. Next, the samples are flushed in iPrOH, transferred to a container of iPrOH, and sonicated for 5 minutes. Finally, the samples are flushed with Ar gas and dried.
[0557] The method of attaching the polymerization initiator is as follows:
[0558] The substrate was placed on a rack and placed in a vacuum oven containing 16 vials of 100 μL CPTMS at approximately 45°C for 150 minutes. The gauge pressure was lowered to -0.96 bar, which caused the CPTMS to evaporate, and the substrate was left for 150 minutes. Afterward, the substrate was removed and placed in an oven at approximately 80°C for 15 minutes to anneale the silane layer. After annealing, the substrate was stored under ambient conditions and left for 24 hours.
[0559] The water contact angle (WCA) was measured to demonstrate the successful attachment of the polymerization initiator (Table 20). The WCA increases significantly from the pre-cleaned Cu substrate of the blank to the Cu with the polymerization initiator attached, which corresponds to the immobilization of hydrophobic molecules.
[0560] Table 20. Measurement of water contact angle before and after CPTMS treatment.
[0561]
Claims
Claim 1 A composite particle comprising: a first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to at least a silicon core; and a silicon core decorated with a second moiety comprising a second anchoring component and a functional group covalently bonded to the silicon core. Claim 2 In claim 1, the composite particle has an average diameter (D) of about 10 nm to about 500 nm as measured by dynamic light scattering. [4,3] Composite particle having 50). Claim 3 In paragraph 1 or 2, the first and second anchoring components are -C ‡ (R A1 )(R A2 )CH(R A3 )-, -C ‡ HCH-, or -C ‡ Selected from MeCH-, where C ‡ represents carbon covalently bonded to the silicon of the Si particle; R A1 , R A2 , R A3 Each is a composite particle independently selected from H or Me. Claim 4 A composite particle according to any one of claims 1 to 3, wherein the polymerization initiator comprises a radical stabilizer and a departure group. Claim 5 In paragraph 3, the polymerization initiator is Rad-LG, where Rad is covalently bonded to the remainder of the first moiety and -(C6(R Rad2 )4)C*(R Rad1 )2, -(C 10 (R Rad2 )6)C*(R Rad1 )2-, -C*(R Rad3 )2, -OC(O)C*(R Rad1 )2, or -NR Rad1 C(O)C*(R Rad1 Selected from )2, where C* represents the carbon attached to LG; each R Rad1 represents independently H or methyl; each R Rad2 is independently H or R Rad3 Represents;R Rad3 represents methyl; LG is a composite particle selected from Cl, Br, or I. Claim 6 In any one of paragraphs 1 to 5, the functional group is H, -C6H5, -C6F5, -C(O)OR FG3 , or represents CN, where R FG3 is a composite particle representing CH3 or tertiary-butyl. Claim 7 A composite particle according to any one of claims 1 to 6, wherein the relative surface stoichiometry of the first moiety is at least 0.5%. Claim 8 In any one of claims 1 to 7, the silicon core is a composite particle comprising crystalline silicon. Claim 9 In any one of claims 1 to 8, the silicon core is an aggregate of particles, said aggregate has an outermost surface and a plurality of inner surfaces, and comprises an outer composite particle and an optionally selected inner particle, wherein The above-mentioned randomly selected internal particle is Includes a silicon core; The above external composite particles are Silicon core; and A composite particle comprising an outer surface region, wherein the outer surface region comprises a region decorated with the first and second moieties covalently bonded to the silicon core of the outer composite particle through the first and second anchoring components; wherein the decorated region of the outer surface region of the outer composite particle forms the outermost surface of the aggregate, and none of the surfaces of the optionally selected inner particles form part of the outermost surface of the aggregate. Claim 10 As a method for forming composite particles, a. a step of providing the following: i. Silicon particles, ii. A first moiety precursor comprising a first anchorable component and a polymerization initiator, and iii. a second moiety precursor comprising a second anchorable component and a functional group; b. a step of decorating the silicon particle by reacting the first anchorable component of the first moiety precursor to form a first anchoring component of the first moiety; and c. a step of reacting the second anchorable component of the second moiety precursor to form a second anchoring component of the second moiety, wherein the first anchoring component and the second anchoring component are covalently bonded to the silicon particle. Claim 11 In claim 10, the method comprises the step of exposing silicon particles to HF to form a Si-H moiety on at least a portion of the surface of the silicon particles before reaction with the first and second moiety precursors. Claim 12 A method according to any one of claims 10 to 11, wherein the first and second moiety precursors are immobilized on the surface of the Si-particle at the same step. Claim 13 A method according to any one of claims 10 to 12, wherein the ratio of the first moiety precursor to the second moiety precursor used to decorate the Si-particle is 1:9 to 9:
1. Claim 14 In any one of claims 10 to 13, the silicon core has an average diameter (D) of about 10 nm to about 500 nm as measured using dynamic light scattering. [4,3] A method of having 50. Claim 15 A method according to any one of claims 10 to 14, wherein the first moiety precursor comprises 4-vinyl benzyl chloride and the second moiety precursor comprises tertiary-butyl acrylate, styrene, pentafluorostyrene, or acrylonitrile. Claim 16 A polymer brush composite particle comprising: a first moiety comprising a first anchoring component and a polymer moiety covalently bonded to at least a silicon core; and a silicon core decorated with a second moiety comprising a second anchoring component and one or more functional groups. Claim 17 In paragraph 16, the polymer moiety is a linear polymer chain having an average length of about 2 repeating units to about 1,000 repeating units, a polymer brush composite particle. Claim 18 A method for forming polymer brush composite particles, wherein the method comprises: a) providing composite particles comprising at least a silicon core decorated therein; A first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to a silicon core; and a) a second moiety comprising a second anchoring component and a functional group covalently bonded to a silicon core; b) forming a polymerization reaction composition comprising one or more polymerization catalysts and one or more monomers; and c) exposing the composite particles to the polymerization reaction composition, the method comprising. Claim 19 In paragraph 18, the polymer brush is synthesized by SIP (surface-initiated polymerization). Claim 20 A method according to claim 18 or 19, wherein the polymerization reaction composition is formed from a polymerization composition comprising at least one dormant transition metal catalyst, an activator comprising an oxygen scavenger, and one or more monomers, wherein the one or more monomers may be provided as part of the polymerization composition, part of the activator, or as a separate composition. Claim 21 An anode comprising a composite particle of any one of paragraphs 1 through 9, paragraph 16, or paragraph 17. Claim 22 A cell comprising the anode of paragraph 21, e.g., a secondary lithium-ion cell. Claim 23 A composite particle comprising: a first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to at least a silicon-carbon composite core; and a silicon-carbon composite core decorated with a second moiety comprising a second anchoring component and a functional group covalently bonded to the silicon-carbon composite core. Claim 24 In claim 23, the Si / C composite is obtained by mixing silicon microparticles and PVDC powder, milling them together to form polymer-coated silicon nanoparticles, subsequently carbonizing to obtain a Si / C composite, and optionally coating the Si / C composite with a graphite-carbon layer via CVD; preparing porous silicon particles by grinding, milling, and etching metallurgical-grade Si chips, coating them with carbon via emulsion polymerization, carbonizing to obtain a Si / C composite, and optionally coating the Si / C composite with a graphite-carbon layer via CVD; producing porous silicon by performing magnesium thermal reduction of silica microparticles, coating the etched product with polyvinylidene chloride (PVDC) via emulsion polymerization, drying the product, and heating it to 900°C in a tubular furnace under an argon atmosphere to obtain a Si / C composite, and optionally coating the Si / C with a graphite-carbon layer via CVD. Composite particles, prepared by coating a composite; or by loading silicon nanoparticles into a tubular furnace and coating them with a graphite carbon layer via CVD. Claim 25 In paragraph 23, the composite particles have an average diameter (D) of about 3 μm to about 15 μm as measured by dynamic light scattering. [4,3] Composite particle having 50). Claim 26 In any one of paragraphs 23 to 25, the first and second anchoring components are -C ‡ (R A1 )(R A2 )CH(R A3 )-, -C ‡ HCH-, or -C ‡ Selected from MeCH-, where C ‡ represents carbon covalently bonded to the graphite carbon layer on the silicon-carbon composite particle; R A1 , R A2 , R A3 Each is a composite particle independently selected from H or Me. Claim 27 A composite particle according to any one of paragraphs 23 to 26, wherein the polymerization initiator comprises a radical stabilizer and a departure group. Claim 28 In paragraph 25, the polymerization initiator is Rad-LG, where Rad is covalently bonded to the remainder of the first moiety and -(C6(R Rad2 )4)C*(R Rad1 )2, -(C 10 (R Rad2 )6)C*(R Rad1 )2-, -C*(R Rad3 )2, -OC(O)C*(R Rad2 )2, or -NR Rad1 C(O)C*(R Rad1 Selected from )2, Here, C* represents the carbon attached to the LG; Each R Rad1 represents H or methyl independently; Each R Rad2 is independently H or R Rad3 Representing; R Rad3 represents methyl LG is a composite particle selected from Cl, Br, or I. Claim 29 In any one of paragraphs 23 through 28, the functional group is H, -C6H5, -C6F5, -C(O)OR FG3 , or represents CN, where R FG3 is a composite particle representing CH3 or tertiary-butyl. Claim 30 A composite particle according to any one of paragraphs 23 to 29, wherein the relative surface stoichiometry of the first moiety is at least 0.5%. Claim 31 In any one of paragraphs 23 to 30, the silicon-carbon composite core comprises a graphite carbon layer on its surface, a composite particle. Claim 32 As a method for forming composite particles, a) a step of providing the following: i. Silicon-carbon composite particles, ii. A first moiety precursor comprising a first anchorable component and a polymerization initiator, and iii. a second moiety precursor comprising a second anchorable component and a functional group; b) a step of decorating the silicon-carbon composite particle by reacting the first anchorable component of the first moiety precursor to form a first anchoring component of the first moiety and reacting the second anchorable component of the second moiety precursor to form a second anchoring component of the second moiety, wherein the first anchoring component and the second anchoring component are covalently bonded to the silicon-carbon composite particle. Claim 33 In paragraph 32, the first and second moiety precursors are immobilized on the surface of silicon-carbon composite particles at the same step, in a method. Claim 34 A method according to claim 32 or 33, wherein the ratio of the first moiety precursor to the second moiety precursor used to decorate the silicon-carbon composite particles is 1:9 to 9:
1. Claim 35 In any one of paragraphs 32 to 34, the silicon-carbon core has an average diameter (D) of about 3 μm to about 15 μm as measured using dynamic light scattering. [4,3] A method of having 50. Claim 36 A method according to any one of claims 32 to 35, wherein the first moiety precursor comprises 4-(chloromethyl)benzenediazonium tetrafluoroborate (CBD) and the second moiety precursor comprises tertiary-butyl acrylate, styrene, pentafluorostyrene, or acrylonitrile. Claim 37 A polymer brush composite particle comprising: a first moiety comprising a first anchoring component and a polymer moiety covalently bonded to at least a silicon-carbon core; and a silicon-carbon composite core decorated with a second moiety comprising a second anchoring component and one or more functional groups. Claim 38 In paragraph 37, the polymer moiety is a linear polymer chain having an average length of about 2 repeating units to about 1,000 repeating units, a polymer brush composite particle. Claim 39 A method for forming polymer brush composite particles, wherein the method comprises a) a step of providing composite particles, wherein the composite particles are at least A first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to a silicon-carbon core; and A method comprising: a) a silicon-carbon core decorated with a second moiety comprising a second anchoring component and a functional group covalently bonded to the silicon-carbon core; b) forming a polymerization reaction composition comprising one or more polymerization catalysts and one or more monomers; and c) exposing the composite particles to the polymerization reaction composition. Claim 40 In paragraph 39, the polymer brush is synthesized by SIP (surface-initiated polymerization). Claim 41 A method according to claim 39 or 40, wherein the polymerization reaction composition is formed from a) a polymerization composition comprising at least one dormant transition metal catalyst, b) an activator comprising an oxygen scavenger, and c) one or more monomers, wherein the one or more monomers may be provided as part of the polymerization composition, part of the activator, or as a separate composition. Claim 42 A polymer brush layer near an electrically conductive support — said polymer brush layer A first moiety comprising a first anchoring component covalently bonded to the electrically conductive support together with a polymerization initiator; and An electrode comprising a second moiety comprising a second anchoring component covalently bonded to the electrically conductive support together with one or more functional groups; and an electroactive layer. Claim 43 In paragraph 42, the electrode comprises an electroactive layer comprising a cathode having a cathode active material such as lithium cobalt oxide (LiCoO2 or LCO), lithium nickel manganese cobalt oxide (LiNiMnCoO2 or NMC), lithium iron phosphate (LiFePO4 or LFP), or lithium nickel cobalt aluminum oxide (LiNiCoAlO2 or NCA); or an anode having an anode active material such as lithium metal or silicon anode. Claim 44 In paragraph 42 or 43, the first and second anchoring components are Si ‡ (R A1 )(R A2 )(R A3 Selected from ), where Si ‡ represents silicon covalently bonded to a partially oxidized surface of an electrically conductive support;R A1 , R A2 , R A3 Each electrode is independently selected from alkoxy groups such as methoxy, ethoxy, iso-propoxy, and butoxy. Claim 45 In paragraph 42 or 43, the polymerization initiator comprises a radical stabilizer and a leaving group, an electrode. Claim 46 In any one of paragraphs 42 to 45, the polymerization initiator is Rad-LG, where Rad is covalently bonded to the remainder of the first moiety and -(C6(R Rad2 )4)C*(R Rad1 )2, -(C 10 (R Rad2 )6)C*(R Rad1 )2-, -C*(R Rad3 )2, -OC(O)C*(R Rad2 )2, or -NR Rad1 C(O)C*(R Rad1 Selected from )2, where C* represents the carbon attached to LG; and each R Rad1 represents independently H or methyl; each R Rad2 is independently H or R Rad3 Represents;R Rad3 represents methyl; LG is an electrode selected from Cl, Br, or I. Claim 47 In any one of paragraphs 42 through 46, the functional group is H, -C6H5, -C6F5, -C(O)OR FG3 , or represents CN, where R FG3 is an electrode representing CH3 or tertiary-butyl. Claim 48 An electrode according to any one of paragraphs 42 to 47, wherein the relative surface stoichiometry of the first moiety is at least 0.5%. Claim 49 A method for forming an electrically conductive support decorated with a polymer brush, comprising the steps of: providing i. an electrically conductive support; ii. a first moiety precursor comprising a first anchorable component and a polymerization initiator; and iii. a second moiety precursor comprising a second anchorable component and a functional group; and decorating the electrically conductive support by reacting the first anchorable component of the first moiety precursor to form a first anchoring component of the first moiety and reacting the second anchorable component of the second moiety precursor to form a second anchoring component of the second moiety, wherein the first anchoring component and the second anchoring component are covalently bonded to the electrically conductive support. Claim 50 In paragraph 49, the first and second moiety precursors are simultaneously immobilized on the surface of an electrically conductive support. Claim 51 A method according to claim 50 or 51, wherein the ratio of the first moiety precursor to the second moiety precursor used to decorate the electrically conductive support is 1:9 to 9:
1. Claim 52 The method of claim 50 or 51, wherein the first moiety precursor comprises (p-chloromethyl)phenyltrimethoxysilane (CPTMS) and 3-trimethoxysilylpropyl 2-bromo-2-methyl-propionate (BPTMS); and the second moiety precursor comprises 4-aminopropyltrimethoxysilane (APTMS). Claim 53 An electrically conductive support decorated with a polymer brush, comprising: a first moiety comprising a first anchoring component and a polymer moiety covalently bonded to at least the electrically conductive support; and a second moiety comprising a second anchoring component and one or more functional groups, wherein the one or more functional groups comprise α-bromoisobutyryl bromide (BiBB), the electrically conductive support decorated with the second moiety. Claim 54 In paragraph 53, an electrically conductive support decorated with polymer brushes, wherein the polymer moiety is a linear polymer chain having an average length of about 2 repeating units to about 1,000 repeating units. Claim 55 A method for forming an electrically conductive support decorated with a polymer brush, wherein the method comprises the step of providing an electrically conductive support, the electrically conductive support A first moiety comprising a first anchoring component and a polymerization initiator covalently bonded to the electrically conductive support; and A method comprising: a step comprising a second moiety comprising a second anchoring component and a functional group covalently bonded to the electrically conductive support; a step of forming a polymerization reaction composition comprising one or more polymerization catalysts and one or more monomers; and a step of exposing the decorated electrically conductive support to the polymerization reaction composition. Claim 56 In paragraph 55, the polymer brush is synthesized by SIP (surface-initiated polymerization). Claim 57 A method according to claim 54 or 55, wherein the polymerization reaction composition is formed from a polymerization composition comprising at least one dormant transition metal catalyst, an activator comprising an oxygen scavenger, and one or more monomers, wherein the one or more monomers may be provided as part of the polymerization composition, part of the activator, or as a separate composition.